Lead-acid battery

By integrating a polymer compound and a specific metal element in the negative electrode material, the lead-acid battery addresses the issue of decreased charge acceptance and hydrogen gas generation, enhancing conductivity and extending battery life.

JP7605107B2Active Publication Date: 2024-12-24GS YUASA CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021521917
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-31
Filing Date
2020-05-29
Publication Date
2024-12-24
Estimated Expiration
2040-05-29

AI Technical Summary

Technical Problem

The inclusion of organic additives in the negative electrode material of lead-acid batteries leads to a decrease in charge acceptance and hydrogen gas generation during overcharging, as the organic additives adhere to the lead surface, inhibiting the elution of lead sulfate and reducing the conductivity of the electrode.

Method used

Incorporating a polymer compound with a chemical shift of 3.2 to 3.8 ppm in the H-NMR spectrum and a metal element (excluding Pb) into the negative electrode material, which forms a composite with lead, enhancing conductivity and suppressing the reduction reaction of hydrogen ions, thereby reducing overcharge and maintaining charge acceptance.

Benefits of technology

The polymer compound and metal element interaction in the negative electrode material suppresses the decrease in charge acceptance and hydrogen gas generation, improving the battery's performance by maintaining conductivity and reducing overcharge, thus extending the battery's life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605107000003
    Figure 0007605107000003
  • Figure 0007605107000001
    Figure 0007605107000001
  • Figure 0007605107000002
    Figure 0007605107000002
Patent Text Reader

Abstract

Provided is a lead-acid battery comprising a positive electrode plate, a negative electrode plate, and an electrolytic solution. The negative electrode plate includes a negative electrode material, wherein the negative electrode material contains a polymer compound and metal elements (excluding Pb). The polymer compound has a peak in the range of 3.2-3.8 ppm in the chemical shift of a 1H-NMR spectrum, or contains a repeating structure of an oxyC2-4 alkylene unit.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lead-acid battery. [Background technology]

[0002] Lead-acid batteries are used in a variety of applications, including automotive and industrial use. Lead-acid batteries include negative and positive plates, separators (or mats), and electrolytes. Additives are sometimes added to the components of lead-acid batteries to impart various functions.

[0003] Patent Document 1 proposes a lead-acid battery characterized in that an activator containing an organic polymer is enclosed in a small sealed container having a cleavage mechanism into the battery case, and the small sealed container is attached to the battery case or the lid.

[0004] Patent Document 2 proposes a fiber-attached mat that includes a plurality of fibers coated with a size composition, a binder composition, and one or more additives, the additives including one or more of rubber additives, rubber derivatives, aldehydes, metal salts, ethylene-propylene oxide block copolymers, sulfates, sulfonates, phosphates, polyacrylic acid, polyvinyl alcohol, lignin, phenol-formaldehyde resins, cellulose, and wood flour, and that can function to reduce water loss in a lead-acid battery.

[0005] Patent Document 3 describes a lead-acid battery in which positive and negative electrode grids are made of a Pb-Ca-Sn alloy and positive and negative electrode connecting members are made of a lead alloy containing 5000 mass ppm or less (including cases where the content is substantially 0) of Sb, characterized in that 0.02 to 0.2 mol / L of aluminum ions are added to the electrolyte, and Sb or a compound thereof is added to the positive electrode active material, negative electrode active material, or electrolyte so that the amount of Sb element is 100 to 1000 mass ppm in terms of the mass ratio to the negative electrode active material.

[0006] Patent Document 4 describes a lead-acid battery in which aluminum is added to the electrolyte, the lead-acid battery being characterized in that aluminum is added to the positive electrode active material layer and / or the negative electrode active material layer of the lead-acid battery.

[0007] Patent Document 5 describes an electrode for a lead-acid battery formed by combining a porous carbon material having a bicontinuous porous structure portion in which a carbon portion and voids each form a continuous structure with lead or a lead compound. Patent Document 5 also describes that the electrode for a lead-acid battery can contain a conductive assistant, a binder, a metal, a metal compound, and the like in addition to the porous carbon material and the lead or lead compound. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2000-149980 A [Patent Document 2] Special Publication No. 2017-525092 [Patent Document 3] JP 2012-89296 A [Patent Document 4] JP 2018-198151 A [Patent Document 5] JP 2017-162754 A (Claim 1, paragraph

[0030] ) Summary of the Invention [Problem to be solved by the invention]

[0009] When an organic additive is contained in the negative electrode material, the organic additive adheres to the surface of the lead. When the surface of the lead is covered with the organic additive, the surface of the lead sulfate generated during discharge is also likely to be covered with the organic additive. As a result, the lead sulfate is less likely to dissolve during charging, and the charge acceptance is reduced. [Means for solving the problem]

[0010] One aspect of the present invention is a battery comprising a positive electrode plate, a negative electrode plate, and an electrolyte solution, The negative electrode plate comprises a negative electrode material, The negative electrode material contains a polymer compound and a metal element (excluding Pb), The polymer compound is 1 The present invention relates to a lead-acid battery having a peak in the range of 3.2 ppm or more and 3.8 ppm or less in the chemical shift of the H-NMR spectrum.

[0011] Another aspect of the present invention is a battery comprising a positive electrode plate, a negative electrode plate, and an electrolyte, The negative electrode plate comprises a negative electrode material, The negative electrode material is a metal element (excluding Pb) and oxy-C 2-4 and a polymer compound containing a repeating structure of alkylene units. Effect of the Invention

[0012] Even when a polymer compound is contained in the negative electrode material of a lead-acid battery, the decrease in charge acceptance can be suppressed. [Brief description of the drawings]

[0013] [Figure 1] 1 is a partially cutaway exploded perspective view showing the appearance and internal structure of a lead-acid battery according to one aspect of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] In general, when an organic additive is contained in the negative electrode material of a lead-acid battery, the organic additive adheres to the surface of the lead, which is the active material. When the surface of the lead is covered with the organic additive, lead sulfate generated during discharge is difficult to dissolve during charging, and the charge acceptance decreases.

[0015] In addition, in general, when the surface of lead is covered with an organic additive, the reduction reaction of hydrogen ions is difficult to occur, so that hydrogen gas generation during overcharging is suppressed and the decrease in electrolyte (hereinafter, sometimes simply referred to as electrolyte decrease) tends to be suppressed. Therefore, there is a trade-off between suppressing the decrease in charge acceptance and suppressing electrolyte decrease, and it has been difficult to achieve both in the past. Furthermore, when the organic additive is unevenly distributed in the pores of the lead, the content of the organic additive in the negative electrode material needs to be increased in order to ensure a sufficient effect of reducing hydrogen gas generation. However, increasing the content of the organic additive significantly reduces charge acceptance.

[0016] In lead-acid batteries, sulfuric acid aqueous solution is generally used as the electrolyte, so if an organic additive (oil, polymer, organic shrinkage inhibitor, etc.) is contained in the negative electrode material, it becomes difficult to balance the elution into the electrolyte and the adsorption to lead. For example, if an organic additive with low adsorption to lead is used, it becomes easy to elute into the electrolyte, making it difficult to suppress the reduction reaction of hydrogen ions. On the other hand, if an organic additive with high adsorption to lead is used, it becomes difficult to adhere thinly to the lead surface, and the organic additive tends to be unevenly distributed in the pores of the lead.

[0017] When organic additives are unevenly distributed within the pores of the lead, the steric hindrance of the unevenly distributed organic additives inhibits the movement of ions (such as lead ions and sulfate ions). This makes it easy for charge and discharge reactions to be inhibited. If the content of the organic additives is increased from the viewpoint of sufficiently ensuring the effect of suppressing the reduction reaction of hydrogen ions, the movement of ions within the pores is further inhibited, and the charge and discharge reactions are further inhibited. For these reasons, the charge acceptance is also likely to decrease.

[0018] In contrast, a lead-acid battery according to one aspect of the present invention includes a positive plate, a negative plate, and an electrolyte. The negative plate includes a negative electrode material, and the negative electrode material includes a polymer compound and a metal element (excluding Pb). The polymer compound includes 1 In the H-NMR spectrum, it has a peak in the range of 3.2 ppm to 3.8 ppm. In addition,1 The peaks appearing in the range of 3.2 ppm to 3.8 ppm in the H-NMR spectrum are oxy-C 2-4 It is derived from an alkylene unit, where 1 H-NMR spectra are measured using deuterated chloroform as the solvent.

[0019] A lead-acid battery according to another aspect of the present invention includes a positive electrode plate, a negative electrode plate, and an electrolyte. The negative electrode plate includes a negative electrode material, and the negative electrode material includes a metal element (excluding Pb) and oxy-C. 2-4 and a polymer compound containing a repeating structure of alkylene units.

[0020] Thus, in the lead-acid battery according to one aspect and another aspect of the present invention, the negative electrode material contains a metal element other than Pb (hereinafter, may be simply referred to as the first metal element) and the above-mentioned polymer compound. By containing not only the polymer compound but also the first metal element in the negative electrode material, it is possible to suppress the decrease in charge acceptance caused by the negative electrode material containing the polymer compound. When the negative electrode material does not contain a polymer compound, the charge acceptance is not affected at all even if the first metal element is added to the negative electrode material. In addition, since the negative electrode material contains a large amount of lead, it is originally highly conductive. However, when the negative electrode material contains a polymer compound, the charge acceptance decreases, so it is considered that the high conductivity of lead is not exhibited and the conductivity of the negative electrode material decreases. When the negative electrode material in such a state contains the first metal element, the decrease in charge acceptance is suppressed. From these facts, it is believed that the reason why the decrease in charge acceptance is suppressed is that the inclusion of the polymer compound and the first metal element in the negative electrode material creates an interaction that cannot be obtained between the polymer compound and lead, and a conductive polymer-metal composite is formed. This interaction suppresses the decrease in the conductivity of lead sulfate even when the negative electrode material contains a polymer compound, making it easier to reduce, and suppresses the decrease in the solubility of lead sulfate during charging, which is believed to result in the suppression of the decrease in charge acceptance.

[0021] In general, in a lead-acid battery, the reaction during overcharging is greatly influenced by the reduction reaction of hydrogen ions at the interface between lead and the electrolyte. In addition, when the negative electrode material contains a first metal element, a side reaction involving the first metal element is likely to occur during overcharging, and the overcharged amount of electricity increases, making it easier for hydrogen gas to be generated. In the lead-acid battery according to one aspect and another aspect of the present invention, even though the negative electrode material contains the first metal element, the overcharged amount of electricity can be reduced, thereby reducing loss of electrolyte. The reason why the overcharged amount of electricity is reduced is believed to be that the surface of the lead, which is the negative electrode active material, is covered with a polymer compound, which increases the hydrogen overvoltage and inhibits the side reaction in which hydrogen is generated from protons during overcharging.

[0022] The polymer compound is OxyC 2-4 It is believed that the alkylene unit makes it easier to form a linear structure, so that it is difficult to remain in the negative electrode material and is easy to diffuse into the electrolyte. Therefore, it is expected that the use of the above-mentioned polymer compound will hardly produce any effect in reducing the amount of electricity in overcharge. However, contrary to such expectations, the present inventors have found that, in fact, even if a very small amount of polymer compound is contained in the negative electrode material, the effect of reducing the amount of electricity in overcharge can be obtained. Since the effect of reducing the amount of electricity in overcharge can be obtained even with a very small amount of polymer compound, by including the polymer compound in the negative electrode material, it is possible to make it exist in the vicinity of lead, and thereby, it is possible to reduce the amount of electricity in overcharge. 2-4 It is believed that the alkylene units exert a high adsorption effect on lead. In addition, the polymer compound spreads thinly on the surface of the lead, and the reduction reaction of hydrogen ions is suppressed over a wide area of ​​the lead surface. This is not inconsistent with the fact that the polymer compound is likely to have a linear structure. In addition, since hydrogen gas generation is suppressed, the loss of electrolyte can be reduced, which is advantageous for extending the life of the lead-acid battery.

[0023] Oxy C 2-4By incorporating a polymer compound having an alkylene unit into the negative electrode material, the lead surface is covered with the polymer compound in a thinly spread state as described above. Therefore, compared to the case of using other organic additives, even if the content in the negative electrode material is small, an excellent effect of reducing the amount of overcharge electricity can be ensured. Since the polymer compound thinly covers the lead surface, the elution of lead sulfate generated during discharge during charging is less likely to be inhibited. In addition, the uneven distribution of the polymer compound in the pores of the lead is suppressed, making it easier for ions to move. From these points of view, the decrease in charge acceptance is suppressed. Therefore, the decrease in charge acceptance can be suppressed while suppressing the generation of hydrogen gas (and further reducing the loss of liquid).

[0024] In order to obtain the above-mentioned effect of the polymer compound, it is necessary to make the polymer compound exist in the vicinity of lead or lead sulfate. Therefore, regardless of whether the components of the lead-acid battery other than the negative electrode material contain a polymer compound, it is important that the negative electrode material contains a polymer compound. And, with such a configuration, it is possible to suppress the decrease in charge acceptance by interacting with the metal element. Furthermore, it is possible to increase the hydrogen overvoltage in the negative plate, and as a result, it is possible to reduce the amount of overcharge electricity.

[0025] In addition, the origin of the polymer compound contained in the negative electrode material is not particularly limited as long as the polymer compound can be contained in the negative electrode material. When producing a lead-acid battery, the polymer compound may be contained in any of the components of the lead-acid battery (e.g., the negative electrode plate, the positive electrode plate, the electrolyte, and / or the separator, etc.). The polymer compound may be contained in one component, or in two or more components (e.g., the negative electrode plate and the electrolyte, etc.).

[0026] In a lead acid battery according to one aspect of the present invention, the polymer compound may include oxygen atoms bonded to end groups and -CH2- and / or -CH< groups bonded to the oxygen atoms. 1In the H-NMR spectrum, the ratio of the integral value of the peak between 3.2 ppm and 3.8 ppm to the total integral value of this peak, the integral value of the peak of the hydrogen atom of the -CH2- group bonded to the oxygen atom, and the integral value of the peak of the hydrogen atom of the -CH< group bonded to the oxygen atom is preferably 85% or more. 2-4 It contains many alkylene units in its molecule. Therefore, it is thought that it is easy to adsorb to lead, and that it is easy to take a linear structure, which makes it easy to thinly cover the lead surface. Therefore, it is possible to more effectively suppress the amount of overcharge electricity. In addition, it is possible to further enhance the effect of suppressing the decrease in charge acceptance.

[0027] 1 Polymer compounds that have a peak in the chemical shift range of 3.2 ppm to 3.8 ppm in the H-NMR spectrum are oxyC 2-4 It is preferable that the alkylene unit contains a repeating structure. 2-4 When a polymer compound containing a repeating structure of alkylene units is used, it is believed that the polymer compound is more easily adsorbed to lead and is more likely to have a linear structure, which makes it easier to thinly cover the lead surface. Therefore, the effect of suppressing the decrease in charge acceptance can be further improved and the amount of electricity in overcharge can be more effectively suppressed.

[0028] In the present specification, the polymer compound is oxyC 2-4 It refers to a polymer having a repeating alkylene unit and / or a number average molecular weight (Mn) of 500 or more.

[0029] In addition, Oxy C 2-4 The alkylene unit is -OR 1 -(R 1 is C 2-4 It is a unit represented by the formula:

[0030] The polymer compound is OxyC 2-4 Ethers of hydroxy compounds with repeating alkylene units and oxy C 2-4The hydroxy compound may include at least one selected from the group consisting of esters of hydroxy compounds having a repeating structure of alkylene units. 2-4 Alkylene glycol, oxy C 2-4 Copolymers containing repeating alkylene units and polyols C 2-4 The polymer compound is at least one selected from the group consisting of alkylene oxide adducts. When such a polymer compound is used, the decrease in charge acceptance can be further suppressed. In addition, since the effect of reducing the amount of electricity during overcharging is high, hydrogen gas generation can be more effectively suppressed and a high effect of suppressing the loss of electrolyte can be obtained.

[0031] Oxy C 2-4 The repeating structure of the alkylene unit may include at least a repeating structure of an oxypropylene unit (-O-CH(-CH3)-CH2-). Such a polymer compound is considered to have an excellent balance between high adsorption to lead and ease of spreading thinly on the lead surface. Therefore, the effect of suppressing the decrease in charge acceptance can be further enhanced, and the amount of electricity in overcharge can be more effectively reduced.

[0032] Thus, since the polymer compound has high adsorption to lead while being able to thinly cover the lead surface, even if the content of the polymer compound in the negative electrode material is relatively small (for example, 400 ppm or less), the decrease in charge acceptance can be suppressed by interaction with the first metal element. In addition, the overcharge charge can be reduced more effectively. The decrease in charge acceptance can also be suppressed because the steric hindrance of the polymer compound in the lead pores can be reduced. From the viewpoint of further enhancing the effect of reducing the overcharge charge, the content of the polymer compound in the negative electrode material is preferably 10 ppm or more.

[0033] The polymer compound preferably contains a compound having at least Mn of 1000 or more. In this case, the polymer compound is likely to remain in the negative electrode material, and the adsorption to lead is increased, so that the polymer compound can continuously interact with the first metal element. Therefore, the decrease in charge acceptance can be continuously suppressed. In addition, the effect of reducing the overcharged amount of electricity is further enhanced. By suppressing the generation of hydrogen gas, the deterioration of the negative electrode active material caused by the collision of hydrogen gas with the negative electrode active material can also be suppressed, which is advantageous for extending the life.

[0034] The first metal element includes, for example, at least one selected from metal elements of groups 3 to 14 of the periodic table. The first metal element may include at least one selected from the group consisting of metal elements of groups 10 and 11 of the periodic table. In particular, the first metal element preferably includes at least one selected from the group consisting of Cu, Ag, and Ni. In these cases, it is possible to more effectively suppress the decrease in charge acceptance, and it is easier to ensure a higher effect of reducing the overcharge electricity quantity.

[0035] The content of the first metal element in the negative electrode material is, for example, 10 ppm to 500 ppm by mass, which can further enhance the effect of suppressing the decrease in charge acceptance and the loss of electrolyte.

[0036] The content of the polymer compound and the concentration of the first metal element in the negative electrode material are each determined for the negative plate of a lead-acid battery in a fully charged state.

[0037] The lead acid battery may be either a valve regulated (sealed) lead acid battery or a flooded (vented) lead acid battery.

[0038] In this specification, the fully charged state of a flooded lead-acid battery is defined by the definition of JIS D 5301:2006. More specifically, the fully charged state is a state in which a lead-acid battery is charged at a current (A) 0.2 times the value listed as the rated capacity (Ah) until the terminal voltage during charging or the electrolyte density converted to a temperature of 20°C, measured every 15 minutes, shows a constant value with three significant digits three times in a row. In addition, in the case of a valve-regulated lead-acid battery, the fully charged state is a state in which constant current and constant voltage charging of 2.23 V / cell is performed in an air tank at 25°C ± 2°C at a current (A) 0.2 times the value listed as the rated capacity (Ah), and charging is terminated when the charging current during constant voltage charging becomes 0.005 times the value listed as the rated capacity (Ah). The value listed as the rated capacity is in Ah units. The unit of current set based on the value listed as the rated capacity is A.

[0039] A fully charged lead-acid battery refers to a lead-acid battery that has already been chemically formed and is fully charged. A lead-acid battery may be fully charged immediately after chemical formation, or after a period of time has passed since chemical formation (for example, a lead-acid battery that has been in use (preferably in the early stages of use) after chemical formation may be fully charged). An early stage battery refers to a battery that has not been in use for very long and has hardly deteriorated at all.

[0040] In this specification, the number average molecular weight Mn is determined by gel permeation chromatography (GPC). The standard substance used in determining Mn is polyethylene glycol.

[0041] Hereinafter, the lead-acid battery according to the embodiment of the present invention will be described in detail with respect to each of its main components, but the present invention is not limited to the following embodiment.

[0042] [Lead acid battery] (Negative plate) A negative electrode plate usually includes a negative electrode current collector in addition to a negative electrode material. The negative electrode material is the negative electrode plate excluding the negative electrode current collector. Note that a member such as a mat or pasting paper may be attached to the negative electrode plate. Such members (attaching members) are used integrally with the negative electrode plate and are therefore included in the negative electrode plate. In addition, when the negative electrode plate includes such members, the negative electrode material is the negative electrode material excluding the negative electrode current collector and the attaching member. However, when an attaching member such as a mat is attached to the separator, the thickness of the attaching member is included in the thickness of the separator.

[0043] The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a negative electrode grid as the negative electrode current collector because it is easy to support the negative electrode material.

[0044] The lead alloy used for the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element. The negative electrode current collector may have a surface layer. The surface layer and the inner layer of the negative electrode current collector may have different compositions. The surface layer may be formed on a part of the negative electrode current collector. The surface layer may be formed on the ear of the negative electrode current collector. The surface layer of the ear may contain Sn or an Sn alloy.

[0045] The negative electrode material includes the above polymer compound. The negative electrode material further includes a negative electrode active material (lead or lead sulfate) that develops capacity through an oxidation-reduction reaction. The negative electrode material may include a shrinkage inhibitor, a carbonaceous material, and / or other additives. Examples of additives include, but are not limited to, barium sulfate and fibers (such as resin fibers). Note that the negative electrode active material in a charged state is sponge-like lead, but an unformed negative plate is usually made using lead powder.

[0046] (first metal element) The first metal element is not particularly limited as long as it is, for example, a metal element other than Pb, and may be either a typical metal element or a transition metal element. The negative electrode material may contain one type of the first metal element, or may contain two or more types of the first metal elements.

[0047] Examples of the first metal element include at least one selected from metal elements in groups 1 to 15 of the periodic table. Examples of the first metal element include metal elements in group 1 of the periodic table (Li, K, etc.), metal elements in group 2 (Mg, Ca, Sr, etc.), metal elements in group 3 (Sc, Y, lanthanides, actinides), metal elements in group 4 (Ti, Zr, etc.), metal elements in group 5 (V, Nb, etc.), metal elements in group 6 (Cr, Mo, W, etc.), metal elements in group 7 (Mn, etc.), metal elements in group 8 (Fe, Ru, etc.), metal elements in group 9 (Co, Rh, Ir, etc.), metal elements in group 10 (Ni, Pd, Pt), metal elements in group 11 (Cu, Ag, Au), metal elements in group 12 (Zn, etc.), metal elements in group 13 (Al, Ga, In, etc.), and metal elements in group 14 (Ge, Sn, Pb).

[0048] The first metal element may be a metal element other than Na and / or Ba. The first metal element may be a metal element other than Group 1 and Group 2 metal elements in the periodic table.

[0049] Among them, the first metal element preferably includes at least one selected from the metal elements of Groups 3 to 14 of the periodic table, and more preferably includes at least one selected from the group consisting of metal elements of Groups 10 and 11. The first metal element further preferably includes at least one selected from the group consisting of Cu, Ag, and Ni. Use of these first metal elements can further enhance the effect of reducing the decrease in charge acceptance and the overcharge electricity quantity.

[0050] The first metal element may be contained in the negative electrode material in the form of a metal or an alloy, or in the form of a compound, or both. From the viewpoint of easily ensuring high conductivity by interaction with the polymer compound, it is preferable that the first metal element is contained in the negative electrode material in a state in which at least a metallic bond is formed (i.e., in the form of a metal or an alloy).

[0051] The average particle size of the metal component (metal, alloy, and compound) containing the first metal element contained in the negative electrode material is, for example, 1 μm or less, may be 500 nm or less, or may be 300 nm or less. The average particle size of the metal component is, for example, 10 nm or more.

[0052] The content of the first metal element in the negative electrode material is, for example, 10 ppm or more, and may be 20 ppm or more, based on mass. From the viewpoint of further enhancing the effect of suppressing the decrease in charge acceptance, the content of the first metal element is preferably 50 ppm or more, and may be 100 ppm or more. The content of the first metal element is, for example, 500 ppm or less. From the viewpoint of further enhancing the effect of reducing the overcharge electricity amount, the content of the first metal element is preferably 200 ppm or less, more preferably 180 ppm or less, and even more preferably 150 ppm or less.

[0053] The content of the first metal element in the negative electrode material may be, by mass, 10 ppm or more (or 20 ppm or more) and 500 ppm or less, 10 ppm or more (or 20 ppm or more) and 200 ppm or less, 10 ppm or more (or 20 ppm or more) and 180 ppm or less, 10 ppm or more (or 20 ppm or more) and 150 ppm or less, 50 ppm or more (or 100 ppm or more) and 500 ppm or less, 50 ppm or more (or 100 ppm or more) and 200 ppm or less, 50 ppm or more (or 100 ppm or more) and 180 ppm or less, or 50 ppm or more (or 100 ppm or more) and 150 ppm or less.

[0054] When the first metal element includes Cu, the content of Cu in the negative electrode material may be 30 ppm or more, 40 ppm or more, 50 ppm or more, or 60 ppm or more, based on mass. When the content of Cu is in such a range, the effect of suppressing the decrease in charge acceptance can be further improved. The content of Cu may be 300 ppm or less, 200 ppm or less, 150 ppm or less, 120 ppm or less, or 100 ppm or less. When the content of Cu is in such a range, the effect of reducing the overcharge electricity quantity can be further improved.

[0055] The Cu content in the negative electrode material may be, by mass, 30 ppm or more (or 40 ppm or more) and 300 ppm or less, 30 ppm or more (or 40 ppm or more) and 200 ppm or less, 30 ppm or more (or 40 ppm or more) and 150 ppm or less, 30 ppm or more (or 40 ppm or more) and 120 ppm or less, 30 ppm or more (or 40 ppm or more) and 100 ppm or less, 50 ppm or more (or 60 ppm or more) and 300 ppm or less, 50 ppm or more (or 60 ppm or more) and 200 ppm or less, 50 ppm or more (or 60 ppm or more) and 150 ppm or less, 50 ppm or more (or 60 ppm or more) and 120 ppm or less, or 50 ppm or more (or 60 ppm or more) and 100 ppm or less.

[0056] When the first metal element includes Ag, the content of Ag in the negative electrode material may be 30 ppm or more, 40 ppm or more, 50 ppm or more, or 80 ppm or more, or 90 ppm or more, based on mass. When the content of Ag is in such a range, the effect of suppressing the decrease in charge acceptance can be further improved. The content of Ag may be 350 ppm or less, 300 ppm or less, 200 ppm or less, or 190 ppm or less, or 180 ppm or less. When the content of Ag is in such a range, the effect of reducing the overcharge electricity quantity can be further improved.

[0057] The Ag content in the negative electrode material is, by mass, 30 ppm or more (or 40 ppm or more) and 350 ppm or less, 30 ppm or more (or 40 ppm or more) and 300 ppm or less, 30 ppm or more (or 40 ppm or more) and 200 ppm or less, 30 ppm or more (or 40 ppm or more) and 190 ppm or less, 30 ppm or more (or 40 ppm or more) and 180 ppm or less, 50 ppm or more (or 80 ppm or more) and 35 ... pm or more (or 80 ppm or more) to 300 ppm or less, 50 ppm or more (or 80 ppm or more) to 200 ppm or less, 50 ppm or more (or 80 ppm or more) to 190 ppm or less, 50 ppm or more (or 80 ppm or more) to 180 ppm or less, 90 ppm or more to 350 ppm or less (or 300 ppm or less), 90 ppm or more to 200 ppm or less (or 190 ppm or less), or 90 ppm or more to 180 ppm or less.

[0058] When the first metal element includes Ni, the Ni content in the negative electrode material may be 10 ppm or more, 15 ppm or more, or 20 ppm or more, based on mass. When the Ni content is in such a range, the effect of suppressing the decrease in charge acceptance can be further improved. The Ni content may be 150 ppm or less, 100 ppm or less, or 70 ppm or less, 60 ppm or less, or 50 ppm or less, or 40 ppm or less, or 30 ppm or less. When the Ni content is in such a range, the effect of reducing the overcharge electricity quantity can be further improved.

[0059] The Ni content in the negative electrode material may be, on a mass basis, 10 ppm or more (or 15 ppm or more) and 150 ppm or less, 10 ppm or more (or 15 ppm or more) and 100 ppm or less, 10 ppm or more (or 15 ppm or more) and 70 ppm or less, 10 ppm or more (or 15 ppm or more) and 60 ppm or less, 10 ppm or more (or 15 ppm or more) and 50 ppm or less, 10 ppm or more (or 15 ppm or more) and 40 ppm or less, 10 ppm or more (or 15 ppm or more) and 30 ppm or less, 20 ppm or more and 150 ppm or less (or 100 ppm or less), 20 ppm or more, 70 ppm or less (or 60 ppm or less), 20 ppm or more and 50 ppm or less (or 40 ppm or less), or 20 ppm or more and 30 ppm or less.

[0060] The first metal element may be contained in the negative electrode material by mixing a metal component containing the first metal element with other components when preparing the negative electrode material. Alternatively, the metal component may be supported on the negative electrode material of the negative plate before or after chemical formation by coating or immersion using a solution or dispersion containing the metal component. The metal component containing the first metal element may be precipitated in the negative electrode material by applying a voltage to the negative plate in a solution containing the metal component (e.g., an electrolyte).

[0061] (Polymer Compound) The polymer compound is 1 In the chemical shift of the H-NMR spectrum, the peak is in the range of 3.2 ppm to 3.8 ppm. 2-4 Contains alkylene units. OxyC 2-4 Examples of the alkylene unit include an oxyethylene unit, an oxypropylene unit, an oxytrimethylene unit, an oxy2-methyl-1,3-propylene unit, an oxy1,4-butylene unit, and an oxy1,3-butylene unit. 2-4 The alkylene unit may have one type or two or more types.

[0062] The polymer compound is OxyC 2-4 It is preferred that the repeating structure of the alkylene unit is a type of oxy C 2-4 It may contain an alkylene unit, and two or more kinds of oxy C 2-4 The polymer compound may contain one type of repeating structure or two or more types of repeating structures.

[0063] Examples of the polymer compound include oxy C 2-4 Poly(C) is a hydroxy compound with repeating alkylene units. 2-4 Alkylene glycol, oxy C 2-4 Copolymers containing repeating alkylene units, polyol C 2-4 alkylene oxide adducts, and ethers or esters of these hydroxy compounds.

[0064] As copolymers, different oxy C 2-4 Copolymers containing alkylene units, polyC 2-4 Alkylene glycol alkyl ether, poly C carboxylic acid 2-4 alkylene glycol ester, etc. The copolymer may be a block copolymer.

[0065] The polyol may be any of aliphatic polyols, alicyclic polyols, aromatic polyols, and heterocyclic polyols. From the viewpoint of facilitating thin spreading of the polymer compound on the lead surface, aliphatic polyols and alicyclic polyols (e.g., polyhydroxycyclohexane, polyhydroxynorbornane, etc.) are preferred, and among them, aliphatic polyols are preferred. Examples of aliphatic polyols include aliphatic diols and polyols with triols or more (e.g., glycerin, trimethylolpropane, pentaerythritol, sugar alcohols, etc.). Examples of aliphatic diols include alkylene glycols with 5 or more carbon atoms. Examples of alkylene glycols include C 5~14Alkylene glycol or C 5-10 The sugar alcohol may be, for example, erythritol, xylitol, mannitol, sorbitol, etc. In the alkylene oxide adduct of the polyol, the alkylene oxide is an oxy C of the polymer compound. 2-4 Corresponding to an alkylene unit, at least C 2-4 In view of the ease with which the polymer compound has a linear structure, the polyol is preferably a diol.

[0066] The etherified product is the above-mentioned oxy C 2-4 At least some of the terminal -OH groups (composed of a hydrogen atom of the terminal group and an oxygen atom bonded to the hydrogen atom) of the hydroxy compound having a repeating structure of alkylene units are etherified to form -OR 2 Groups, where R 2 is an organic group.) Some or all of the terminals of the polymer compound may be etherified. For example, one terminal of the main chain of a linear polymer compound is an -OH group and the other terminal is an -OR group. 2 It may also be a group.

[0067] The esterified product is the above-mentioned oxy C 2-4 At least some of the terminal -OH groups (composed of a hydrogen atom of the terminal group and an oxygen atom bonded to this hydrogen atom) of a hydroxy compound having a repeating structure of an alkylene unit are esterified to form -OC(=O)-R 3 Groups, where R 3 is an organic group.) Some or all of the terminals of the polymer compound may be esterified. For example, one terminal of the main chain of a linear polymer compound is an -OH group and the other terminal is an -OC(=O)-R 3 It may also be a group.

[0068] organic group R 2 and R 3Each of the above groups includes a hydrocarbon group. The hydrocarbon group may have a substituent (e.g., a hydroxy group, an alkoxy group, and / or a carboxy group). The hydrocarbon group may be any of aliphatic, alicyclic, and aromatic. The aromatic hydrocarbon group and the alicyclic hydrocarbon group may have an aliphatic hydrocarbon group (e.g., an alkyl group, an alkenyl group, an alkynyl group) as a substituent. The number of carbon atoms in the aliphatic hydrocarbon group as a substituent may be, for example, 1 to 20, 1 to 10, 1 to 6, or 1 to 4.

[0069] Examples of the aromatic hydrocarbon group include aromatic hydrocarbon groups having 24 or less carbon atoms (e.g., 6 to 24). The number of carbon atoms in the aromatic hydrocarbon group may be 20 or less (e.g., 6 to 20), 14 or less (e.g., 6 to 14), or 12 or less (e.g., 6 to 12). Examples of the aromatic hydrocarbon group include aryl groups and bisaryl groups. Examples of the aryl group include phenyl groups and naphthyl groups. Examples of the bisaryl group include monovalent groups corresponding to bisarenes. Examples of bisarenes include biphenyl, bisarylalkanes (e.g., bisC 6-10 Aryl C 1-4 Alkanes (such as 2,2-bisphenylpropane, etc.) are examples.

[0070] Examples of the alicyclic hydrocarbon group include alicyclic hydrocarbon groups having 16 or less carbon atoms. The alicyclic hydrocarbon group may be a cross-linked cyclic hydrocarbon group. The number of carbon atoms in the alicyclic hydrocarbon group may be 10 or less or 8 or less. The number of carbon atoms in the alicyclic hydrocarbon group may be, for example, 5 or more, or 6 or more.

[0071] The alicyclic hydrocarbon group may have 5 (or 6) or more and 16 (or less), 5 (or 6) or more and 10 (or less), or 5 (or 6) or more and 8 (or less) carbon atoms.

[0072] Examples of alicyclic hydrocarbon groups include cycloalkyl groups (cyclopentyl, cyclohexyl, cyclooctyl, etc.), cycloalkenyl groups (cyclohexenyl, cyclooctenyl, etc.), etc. Alicyclic hydrocarbon groups also include hydrogenated products of the above aromatic hydrocarbon groups.

[0073] From the viewpoint of facilitating thin adhesion of the polymer compound to the lead surface, among the hydrocarbon groups, an aliphatic hydrocarbon group is preferred. Examples of the aliphatic hydrocarbon group include an alkyl group, an alkenyl group, an alkynyl group, and a dienyl group. The aliphatic hydrocarbon group may be either a straight chain or a branched chain.

[0074] The number of carbon atoms in the aliphatic hydrocarbon group is, for example, 30 or less, and may be 26 or less or 22 or less, 20 or less or 16 or less, 14 or less or 10 or less, or 8 or less or 6 or less. The lower limit of the number of carbon atoms depends on the type of the aliphatic hydrocarbon group, being 1 or more for alkyl groups, 2 or more for alkenyl groups and alkynyl groups, and 3 or more for dienyl groups. Among these, alkyl groups and alkenyl groups are preferred from the viewpoint of facilitating thin adhesion of the polymer compound to the lead surface.

[0075] Specific examples of alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, i-pentyl, s-pentyl, 3-pentyl, t-pentyl, n-hexyl, 2-ethylhexyl, n-octyl, n-decyl, i-decyl, lauryl, myristyl, cetyl, stearyl, and behenyl.

[0076] Specific examples of the alkenyl group include vinyl, 1-propenyl, allyl, palmitoleyl, and oleyl. The alkenyl group is, for example, 2-30 Alkenyl group or C 2-26 may be an alkenyl group, C 2-22 Alkenyl group or C 2-20 may be an alkenyl group, C 10-20 It may be an alkenyl group.

[0077] Among the polymer compounds, oxy C 2-4 Ethers of hydroxy compounds having repeating alkylene units and / or oxy C 2-4 The use of an ester of a hydroxy compound having a repeating alkylene unit structure is preferable because it can further enhance the effect of suppressing the decrease in charge acceptance. In addition, even when these polymer compounds are used, a high effect of suppressing the decrease in the electrolyte can be ensured.

[0078] The negative electrode material may contain one type of polymer compound or two or more types of polymer compounds.

[0079] From the viewpoint of further enhancing the effect of reducing the amount of overcharge electricity and suppressing the decrease in charge acceptance, Oxy C 2-4 It is preferable that the repeating alkylene unit contains at least a repeating oxypropylene unit. 1 In the chemical shift of the H-NMR spectrum, peaks due to -CH< and -CH2- of the oxypropylene unit are present in the range of 3.2 ppm to 3.8 ppm. The peaks are split due to differences in electron density around the nuclei of the hydrogen atoms in these groups. Such a polymer compound is 1 In the chemical shift of the H-NMR spectrum, for example, there are peaks in the range of 3.2 ppm to 3.42 ppm and in the range of more than 3.42 ppm to 3.8 ppm. The peak in the range of 3.2 ppm to 3.42 ppm is derived from -CH2-, and the peak in the range of more than 3.42 ppm to 3.8 ppm is derived from -CH< and -CH2-.

[0080] Examples of such polymer compounds include polypropylene glycol, copolymers containing a repeating unit of oxypropylene, propylene oxide adducts of the above polyols, and ethers or esters thereof. Examples of the copolymers include oxypropylene-oxyalkylene copolymers (wherein the oxyalkylene is a C alkylene other than oxypropylene). 2-4 Examples of the oxypropylene-oxyalkylene copolymer include oxypropylene-oxyethylene copolymer and oxypropylene-oxytrimethylene copolymer. The oxypropylene-oxyalkylene copolymer may be a block copolymer.

[0081] In a polymer compound containing a repeating oxypropylene structure, the proportion of the oxypropylene unit is, for example, 5 mol % or more, and may be 10 mol % or more, or 20 mol % or more.

[0082] The polymer compound is selected from the viewpoints of increasing the adsorption ability to lead and of making it easier to form a linear structure, and is therefore an oxy-C 2-4 It is preferable that the polymer compound contains a large number of alkylene units. Such a polymer compound contains, for example, an oxygen atom bonded to the end group and a -CH2- group and / or a -CH< group bonded to the oxygen atom. 1 In the H-NMR spectrum, the integral value of the peak at 3.2 ppm to 3.8 ppm accounts for a large proportion of the total integral value of this peak, the integral value of the peak of the hydrogen atom of the -CH2- group, and the integral value of the peak of the hydrogen atom of the -CH< group. This proportion is, for example, 50% or more, and may be 80% or more. From the viewpoint of further enhancing the effect of reducing the overcharge electricity quantity and further enhancing the effect of suppressing the deterioration of the charge acceptance and / or the low-temperature HR discharge performance, the above proportion is preferably 85% or more, and more preferably 90% or more. For example, when a polymer compound has an -OH group at its terminal and a -CH2- group or a -CH< group bonded to the oxygen atom of the -OH group, 1In the H-NMR spectrum, the peaks of the hydrogen atoms of the -CH2- group and -CH< group have chemical shifts in the range of more than 3.8 ppm to 4.0 ppm.

[0083] The polymer compound may include a compound having an Mn of 500 or more, may include a compound having an Mn of 600 or more, or may include a compound having an Mn of 1000 or more. The Mn of such a compound is, for example, 20000 or less, or may be 15000 or less, or 10000 or less. From the viewpoint of making it easier to retain the compound in the negative electrode material and to spread more thinly on the lead surface, the Mn of the above compound is preferably 5000 or less, and may be 4000 or less, or 3000 or less.

[0084] The Mn of the above compounds may be 500 or more (or 600 or more) and 20,000 or less, 500 or more (or 600 or more) and 15,000 or less, 500 or more (or 600 or more) and 10,000 or less, 500 or more (or 600 or more) and 5,000 or less, 500 or more (or 600 or more) and 4,000 or less, 500 or more (or 600 or more) and 3,000 or less, 1,000 or more and 20,000 or less (or 15,000 or less), 1,000 or more and 10,000 or less (or 5,000 or less), or 1,000 or more and 4,000 or less (or 3,000 or less).

[0085] The polymer compound preferably contains at least a compound having an Mn of 1000 or more. The Mn of such a compound may be 1000 or more and 20000 or less, 1000 or more and 15000 or less, or 1000 or more and 10000 or less. From the viewpoint of making it easier to hold the compound in the negative electrode material and to spread thinly on the lead surface, the Mn of the above compound is preferably 1000 or more and 5000 or less, may be 1000 or more and 4000 or less, or may be 1000 or more and 3000 or less. When using such a compound having Mn, the overcharge quantity of electricity can be more easily reduced. In addition, by reducing the overcharge quantity of electricity, the deterioration of the negative electrode active material caused by the collision of hydrogen gas with the negative electrode active material can be suppressed, which is advantageous for extending the life. The compound having Mn as described above is easy to move into the negative electrode material even when contained in the electrolyte, so that the compound can be replenished in the negative electrode material, and from this viewpoint, it is easy to hold the compound in the negative electrode material. As the polymer compound, two or more compounds having different Mn may be used. In other words, the polymer compound may have a plurality of Mn peaks in the molecular weight distribution.

[0086] The content of the polymer compound in the negative electrode material is, for example, 10 ppm or more, preferably 20 ppm or more or 30 ppm or more, and more preferably 40 ppm or more, based on mass. When the content of the polymer compound is in such a range, it is easier to increase the hydrogen generation voltage and more easily reduce the overcharged amount of electricity. The content of the polymer compound in the negative electrode material (based on mass) is, for example, 500 ppm or less, and may be 400 ppm or less. When the content of the polymer compound is in such a range, the surface of the lead is prevented from being excessively covered with the polymer compound, so that the decrease in charge acceptance can be more effectively suppressed. From the viewpoint of easily ensuring a higher charge acceptance, the content of the polymer compound (based on mass) is preferably 320 ppm or less or 300 ppm or less, and may be 200 ppm or less or 150 ppm or less, or may be 130 ppm or less. These lower and upper limits can be combined arbitrarily.

[0087] The content of polymer compounds (by mass) is 10 ppm or more (or 20 ppm or more) but not more than 500 ppm, 10 ppm or more (or 20 ppm or more) but not more than 400 ppm, 10 ppm or more (or 20 ppm or more) but not more than 320 ppm, 10 ppm or more (or 20 ppm or more) but not more than 300 ppm, 10 ppm or more (or 20 ppm or more) but not more than 200 ppm, 10 ppm or more (or 20 ppm or more) but not more than 150 ppm, 10 ppm or more (or 20 ppm or more) but not more than 130 ppm. ppm or less, 30 ppm or more (or 40 ppm or more) but not more than 500 ppm, 30 ppm or more (or 40 ppm or more) but not more than 400 ppm, 30 ppm or more (or 40 ppm or more) but not more than 320 ppm, 30 ppm or more (or 40 ppm or more) but not more than 300 ppm, 30 ppm or more (or 40 ppm or more) but not more than 200 ppm, 30 ppm or more (or 40 ppm or more) but not more than 150 ppm, or 30 ppm or more (or 40 ppm or more) but not more than 130 ppm.

[0088] In addition, the mass ratio of the first metal element to the polymer compound contained in the negative electrode material (=first metal element / polymer compound) is, for example, 0.12 or more, and may be 0.15 or more or 0.25 or more, or 0.75 or more or 1.25 or more. When the mass ratio is in such a range, the effect of suppressing the decrease in charge acceptance can be further improved. The mass ratio is, for example, 2.5 or less, and may be 2.0 or less or 1.5 or less. When the mass ratio is in such a range, the effect of reducing the overcharge electricity quantity can be further improved.

[0089] The mass ratio of the first metal element to the polymer compound may be 0.12 or more (or 0.15 or more) and 2.5 or less, 0.12 or more (or 0.15 or more) and 2.0 or less, 0.12 or more (or 0.15 or more) and 1.5 or less, 0.25 or more (or 0.75 or more) and 2.5 or less, 0.25 or more (or 0.75 or more) and 2.0 or less, 0.25 or more (or 0.75 or more) and 1.5 or less, 1.25 or more and 2.5 or less (or 2.0 or less), or 1.25 or more and 1.5 or less.

[0090] When the first metal element contains Cu, the mass ratio of Cu to the polymer compound (=Cu / polymer compound) is, for example, 0.1 or more, may be 0.2 or more or 0.3 or more, may be 0.4 or more or 0.5 or more, or may be 0.7 or more. When the mass ratio is in such a range, the effect of suppressing the decrease in charge acceptance can be further improved. The mass ratio of Cu is preferably 2.3 or less, more preferably 1.6 or less or 1.5 or less, and even more preferably 1.25 or less. When the mass ratio is in such a range, the effect of reducing the overcharge electricity quantity can be further improved.

[0091] The mass ratio of Cu to the polymer compound may be 0.1 to 2.3 (or 1.6 or less), 0.2 to 2.3 (or 1.6 or less), 0.3 to 2.3 (or 1.6 or less), 0.4 to 2.3 (or 1.6 or less), 0.5 to 2.3 (or 1.6 or less), 0.7 to 2.3 (or 1.6 or less), 0.1 to 1.5 (or 1.25 or less), 0.2 to 1.5 (or 1.25 or less), 0.3 to 1.5 (or 1.25 or less), 0.4 to 1.5 (or 1.25 or less), 0.5 to 1.5 (or 1.25 or less), or 0.7 to 1.5 (or 1.25 or less).

[0092] When the first metal element includes Ag, the mass ratio of Ag to the polymer compound may be, for example, 0.2 or more, 0.25 or more, or 0.5 or more. When the mass ratio of Ag is in such a range, the effect of suppressing the decrease in charge acceptance can be further improved. The mass ratio of Ag is, for example, 2.5 or less, and may be 2.3 or less, or 2 or less, or 1.5 or less. When the mass ratio of Ag is in such a range, the effect of reducing the overcharge electricity quantity can be further improved.

[0093] The mass ratio of Ag to the polymer compound may be 0.2 or more and 2.5 or less (or 2.3 or less), 0.25 or more and 2.5 or less (or 2.3 or less), 0.5 or more and 2.5 or less (or 2.3 or less), 0.2 or more and 2 or less (or 1.5 or less), 0.25 or more and 2 or less (or 1.5 or less), or 0.5 or more and 2 or less (or 1.5 or less).

[0094] When the first metal element includes Ni, the mass ratio of Ni to the polymer compound may be 0.05 or more, or 0.1 or more. When the mass ratio of Ni is in such a range, the effect of suppressing the decrease in charge acceptance can be further improved. The mass ratio of Ni may be 1 or less, or 0.7 or less, or 0.5 or less. When the mass ratio of Ni is in such a range, the effect of reducing the overcharge electricity quantity can be further improved.

[0095] The mass ratio of Ni to the polymer compound may be 0.05 or more (or 0.1 or more) and 1 or less, 0.05 or more (or 0.1 or more) and 0.7 or less, or 0.05 or more (or 0.1 or more) and 0.5 or less.

[0096] (Shrinkage inhibitor) The negative electrode material may contain a shrinkage inhibitor. As the shrinkage inhibitor, an organic shrinkage inhibitor is preferable. As the organic shrinkage inhibitor, lignins and / or synthetic organic shrinkage inhibitors may be used. As the lignins, lignin, lignin derivatives, etc. may be used. As the lignin derivatives, lignin sulfonic acid or its salts (alkali metal salts (sodium salts, etc.) etc.) may be used. The organic shrinkage inhibitors are generally broadly classified into lignins and synthetic organic shrinkage inhibitors. It can also be said that the synthetic organic shrinkage inhibitor is an organic shrinkage inhibitor other than lignins. The synthetic organic shrinkage inhibitor is an organic polymer containing a sulfur element, and generally contains a plurality of aromatic rings in the molecule and contains a sulfur element as a sulfur-containing group. Among the sulfur-containing groups, a sulfonic acid group or a sulfonyl group, which are stable forms, is preferable. The sulfonic acid group may exist in an acid form or in a salt form such as a Na salt. The negative electrode material may contain one type of shrinkage inhibitor, or may contain two or more types of shrinkage inhibitors. For example, the negative electrode material may include a synthetic organic shrink-proofing agent or a lignin, or may include a synthetic organic shrink-proofing agent and a lignin.

[0097] As the organic shrink-proofing agent, it is preferable to use a condensation product containing at least an aromatic compound unit. For example, such a condensation product may be a condensation product of an aromatic compound with an aldehyde compound (aldehyde (e.g., formaldehyde) and / or its condensation product). The organic shrink-proofing agent may contain one type of aromatic compound unit, or may contain two or more types of aromatic compound units. The aromatic compound unit refers to a unit derived from an aromatic compound incorporated in the condensation product.

[0098] Examples of the aromatic rings that aromatic compounds have include benzene rings and naphthalene rings. When aromatic compounds have multiple aromatic rings, the multiple aromatic rings may be linked by direct bonds or linking groups (e.g., alkylene groups (including alkylidene groups), sulfone groups, etc.). Examples of such structures include bisarene structures (biphenyl, bisphenylalkane, bisphenylsulfone, etc.). Examples of aromatic compounds include compounds having the above aromatic rings and hydroxyl groups and / or amino groups. The hydroxyl groups and amino groups may be directly bonded to the aromatic rings, or may be bonded as alkyl chains having hydroxyl groups and amino groups. The hydroxyl groups include salts of hydroxyl groups (-OMe). The amino groups include salts of amino groups (salts with anions). Examples of Me include alkali metals (Li, K, Na, etc.) and metals in Group 2 of the periodic table (Ca, Mg, etc.).

[0099] As the aromatic compound, bisarene compounds [bisphenol compounds, hydroxybiphenyl compounds, bisarene compounds having an amino group (bisarylalkane compounds having an amino group, bisarylsulfone compounds having an amino group, biphenyl compounds having an amino group, etc.), hydroxyarene compounds (hydroxynaphthalene compounds, phenol compounds, etc.), aminoarene compounds (aminonaphthalene compounds, aniline compounds (aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc.)), etc.] are preferred. The aromatic compound may further have a substituent. The organic shrinkage inhibitor may contain one or more of the residues of these compounds. As the bisphenol compound, bisphenol A, bisphenol S, bisphenol F, etc. are preferred.

[0100] The condensate preferably contains at least a unit of an aromatic compound having a sulfur-containing group. In particular, when a condensate containing at least a unit of a bisphenol compound having a sulfur-containing group is used, the effect of suppressing the decrease in low-temperature HR discharge performance after a high-temperature light-load test can be enhanced. From the viewpoint of enhancing the effect of suppressing the decrease in the liquid, it is preferable to use a condensate of an aldehyde compound with a naphthalene compound having a sulfur-containing group and a hydroxyl group and / or an amino group.

[0101] The sulfur-containing group may be directly bonded to an aromatic ring contained in the compound, or may be bonded to the aromatic ring as an alkyl chain having a sulfur-containing group. The sulfur-containing group is not particularly limited, and examples thereof include a sulfonyl group, a sulfonic acid group, or a salt thereof.

[0102] Also, as the organic shrink-proofing agent, for example, at least one condensate containing at least one selected from the group consisting of the above-mentioned bisarene compound units and monocyclic aromatic compound units (hydroxyarene compounds and / or aminoarene compounds, etc.) may be used. The organic shrink-proofing agent may at least contain a condensate containing a bisarene compound unit and a monocyclic aromatic compound unit (particularly, a hydroxyarene compound). Such a condensate may be a condensate of a bisarene compound and a monocyclic aromatic compound with an aldehyde compound. As the hydroxyarene compound, a phenolsulfonic acid compound (such as phenolsulfonic acid or a substituted product thereof) is preferable. As the aminoarene compound, aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc. are preferable. As the monocyclic aromatic compound, a hydroxyarene compound is preferable.

[0103] The sulfur element content of the organic shrinkage inhibitor is not particularly limited, but from the viewpoint of further enhancing the effect of suppressing liquid loss, it is preferably 9000 μmol / g or less, more preferably 8000 μmol / g or less or 7000 μmol / g or less. The sulfur element content of the organic shrinkage inhibitor is, for example, 400 μmol / g or more.

[0104] The content of sulfur element in an organic shrink-preventer being X μmol / g means that the content of sulfur element contained in 1 g of the organic shrink-preventer is X μmol.

[0105] The weight average molecular weight (Mw) of the organic shrink-proofing agent is, for example, 100,000 or less, and may be 20,000 or less. The Mw of the organic shrink-proofing agent is, for example, 3,000 or more.

[0106] In this specification, the Mw of the organic shrink-preventing agent is determined by GPC. The standard substance used in determining Mw is sodium polystyrene sulfonate.

[0107] The content of the organic shrink-proofing agent in the negative electrode material is, for example, 0.01% by mass or more, and may be 0.05% by mass or more.The content of the organic shrink-proofing agent is, for example, 1.0% by mass or less, and may be 0.5% by mass or less.

[0108] The content of the organic shrinkage inhibitor in the negative electrode material may be 0.01% by mass or more and 1.0% by mass or less, 0.05% by mass or more and 1.0% by mass or less, 0.01% by mass or more and 0.5% by mass or less, or 0.05% by mass or more and 0.5% by mass or less.

[0109] (carbonaceous material) Carbonaceous materials contained in the negative electrode material can be carbon black, graphite, hard carbon, soft carbon, etc. Examples of carbon black include acetylene black, ketjen black, furnace black, and lamp black. Graphite may be any carbonaceous material containing a graphite-type crystal structure, and may be either artificial graphite or natural graphite. The carbonaceous material may be used alone or in combination of two or more.

[0110] The content of the carbonaceous material in the negative electrode material is, for example, 0.05% by mass or more, and may be 0.10% by mass or more. The content of the carbonaceous material is, for example, 5% by mass or less, and may be 3% by mass or less. These lower and upper limits can be combined in any desired manner.

[0111] The content of the carbonaceous material in the negative electrode material may be 0.05% by mass to 5% by mass, 0.05% by mass to 3% by mass, 0.10% by mass to 5% by mass, or 0.10% by mass to 3% by mass.

[0112] (Barium Sulfate) The content of barium sulfate in the negative electrode material is, for example, 0.05% by mass or more, and may be 0.10% by mass or more. The content of barium sulfate in the negative electrode material is 3% by mass or less, and may be 2% by mass or less. These lower and upper limits can be combined in any desired manner.

[0113] The content of barium sulfate in the negative electrode material may be from 0.05 to 3% by mass, from 0.05 to 2% by mass, from 0.10 to 3% by mass, or from 0.10 to 2% by mass.

[0114] (Analysis of the components of negative electrode materials) The following describes a method for analyzing the negative electrode material or its components. Prior to the analysis, the lead-acid battery after chemical formation is fully charged and then disassembled to obtain the negative plate to be analyzed. The obtained negative plate is washed with water to remove sulfuric acid from the negative plate. The washing is performed by pressing a pH test paper against the washed surface of the negative plate until it is confirmed that the color of the test paper does not change. However, the washing time is within 2 hours. The washed negative plate is dried at 60±5°C for about 6 hours under a reduced pressure environment. If an attached material is included after drying, the attached material is removed from the negative plate by peeling. Next, the negative electrode material is separated from the negative plate to obtain a sample (hereinafter also referred to as sample A). Sample A is crushed as necessary and subjected to analysis.

[0115] (1) Analysis of polymer compounds (1-1) Qualitative analysis of polymer compounds 150.0±0.1mL of chloroform is added to 100.0±0.1g of the ground sample A, and the mixture is stirred at 20±5℃ for 16 hours to extract the polymer compound. The solid matter is then removed by filtration. The polymer compound obtained by extracting the chloroform solution in which the polymer compound is dissolved or by drying the chloroform solution is identified by obtaining information from infrared spectroscopy, ultraviolet-visible absorption spectroscopy, NMR spectroscopy, LC-MS and / or pyrolysis GC-MS.

[0116] The chloroform soluble matter is recovered by distilling off the chloroform under reduced pressure from the chloroform solution in which the polymer compound obtained by extraction is dissolved. The chloroform soluble matter is dissolved in deuterated chloroform and then subjected to the following conditions: 1 1H-NMR spectrum is measured. 1 From the H-NMR spectrum, a peak with a chemical shift in the range of 3.2 ppm to 3.8 ppm is confirmed. Also, from the peak in this range, oxy C 2-4 Identify the type of alkylene unit.

[0117] Equipment: AL400 nuclear magnetic resonance equipment manufactured by JEOL Ltd. Observation frequency: 395.88MHz Pulse width: 6.30μs Pulse repetition time: 74.1411 seconds Accumulation count: 32 Measurement temperature: room temperature (20~35℃) Standard: 7.24ppm Sample tube diameter: 5mm

[0118] 1 From the H-NMR spectrum, the integral value (V1) of the peaks present in the chemical shift range of 3.2 ppm to 3.8 ppm is calculated. In addition, for each of the hydrogen atoms of the -CH2- group and -CH< group bonded to the oxygen atom bonded to the terminal group of the polymer compound, 1The sum (V2) of the integral values ​​of the peaks in the H-NMR spectrum is calculated. Then, from V1 and V2, the percentage of V1 in the sum of V1 and V2 (=V1 / (V1+V2)×100(%)) is calculated.

[0119] In addition, in the qualitative analysis, 1 When calculating the integral value of a peak in a H-NMR spectrum, 1 In the H-NMR spectrum, two points without significant signals are determined so as to sandwich the corresponding peak, and each integral value is calculated using a straight line connecting these two points as a baseline. For example, for a peak that exists in a chemical shift range of 3.2 ppm to 3.8 ppm, a straight line connecting two points on the spectrum between 3.2 ppm and 3.8 ppm is used as the baseline. For example, for a peak that exists in a chemical shift range of more than 3.8 ppm to 4.0 ppm, a straight line connecting two points on the spectrum between 3.8 ppm and 4.0 ppm is used as the baseline.

[0120] (1-2) Quantitative analysis of polymer compounds The appropriate amount of the chloroform soluble matter was measured with an accuracy of ±0.0001 g. r (g) Dissolve in deuterated chloroform together with tetrachloroethane (TCE), 1 Measure the H-NMR spectrum. The integral value (S a ) and the integral value of the peak due to TCE (S r ) and calculate the mass-based content C of the polymer compound in the negative electrode material from the following formula: n Calculate the ppm.

[0121] C n =S a / S r ×N r / N a ×M a / M r ×m r / m×1000000 (In the formula, M aThe molecular weight of the structure that shows a peak in the chemical shift range of 3.2 to 3.8 ppm (more specifically, oxy C 2-4 (the molecular weight of the repeating structure of alkylene units) and N a is the number of hydrogen atoms attached to the carbon atoms in the main chain of the repeating unit. r、 M r are the number of hydrogen atoms contained in the molecule of the reference material, the molecular weight of the reference material, and m (g) is the mass of the negative electrode material used for extraction.) In addition, the standard substance in this analysis is TCE, so N r =2, M r = 168. Also, m = 100.

[0122] For example, if the polymer compound is polypropylene glycol, M a is 58, and N a is 3. If the polymer compound is polyethylene glycol, M a is 44, and N a is 4. In the case of copolymers, N a is the N of each monomer unit a The value is calculated by averaging the molar ratio (mol%) of each monomer unit contained in the repeating structure, and M a is determined depending on the type of each monomer unit.

[0123] In addition, in the quantitative analysis, 1 The integral value of the peak in the H-NMR spectrum is determined using data processing software “ALICE” manufactured by JEOL Ltd.

[0124] (1-3) Mn measurement of polymer compounds GPC measurement of polymer compounds is performed using the following equipment under the following conditions. Separately, a calibration curve (calibration curve) is created by plotting the Mn of the standard substance versus elution time. Based on this calibration curve and the GPC measurement results of the polymer compounds, the Mn of the polymer compounds is calculated.

[0125] Analysis system: 20A system (Shimadzu Corporation) Column: Two GPC KF-805L (Shodex) columns connected in series Column temperature: 30℃ Mobile phase: Tetrahydrofuran Flow rate: 1mL / min. Concentration: 0.20% by mass Injection volume: 10μL Standard substance: polyethylene glycol (Mn=200,0000, 20,0000, 20,000, 2,000, 200) Detector: Differential refractive index detector (Shodex RI-201H)

[0126] (2) Analysis of the first metallic element (2-1) Qualitative and quantitative analysis of the first metallic element A specified amount of sample A is dissolved in a 15% by mass aqueous solution of nitric acid. 20 mL of the resulting solution is collected, and ion-exchanged water is added to make the total volume 100 mL. The type of metal in the solution is identified and the emission intensity of the metal is measured by high-frequency inductively coupled plasma (ICP) emission spectroscopy. The mass of the metal contained in the solution is calculated from the measured emission luminosity and a calibration curve prepared in advance, and the proportion of the metal contained in the negative electrode material is calculated. Qualitative and quantitative analysis are performed. The ICPS-8000 manufactured by Shimadzu Corporation is used as the ICP emission spectroscopy measurement device.

[0127] (2-2) Average particle size of the metal component containing the first metal element In an image of sample A taken using a field emission scanning electron microscope (FE-SEM), 100 particles of metal components are arbitrarily selected. The diameter of a circle having the same area as the area enclosed by the outer edge of each particle is calculated and regarded as the particle size of each particle. The average particle size is determined by averaging the particle sizes of each particle.

[0128] (3) Analysis of organic shrinkage inhibitors (3-1) Qualitative analysis of organic shrinkage inhibitors in negative electrode materials Sample A is immersed in a 1 mol / L aqueous solution of sodium hydroxide (NaOH) to extract the organic shrink-preventing agent. Next, insoluble components are removed by filtration from the NaOH aqueous solution containing the extracted organic shrink-preventing agent, and the obtained filtrate is desalted by dialysis, concentrated, and dried. Desalting is performed using a desalting column, by passing the filtrate through an ion exchange membrane, or by placing the filtrate in a dialysis tube and immersing it in distilled water. A powder sample of the organic shrink-preventing agent is obtained by drying this.

[0129] The type of organic shrink-preventing agent is identified by combining information obtained from an infrared spectrum measured using a powder sample of the organic shrink-preventing agent thus obtained, an ultraviolet-visible absorption spectrum measured using an ultraviolet-visible spectrometer after diluting the powder sample with distilled water or the like, and an NMR spectrum of the solution obtained by dissolving the powder sample in a specific solvent such as heavy water.

[0130] (3-2) Quantitative determination of organic shrinkage inhibitor content in negative electrode material As in the above (3-1), a filtrate of the NaOH aqueous solution containing the organic shrinkage inhibitor is obtained, and then the UV-visible absorption spectrum of the filtrate is measured. The content of the organic shrinkage inhibitor in the negative electrode material is quantified using the spectrum intensity and a previously prepared calibration curve.

[0131] In addition, when a lead-acid battery with an unknown content of organic shrink-proofing agent is obtained and the content of the organic shrink-proofing agent is measured, the structural formula of the organic shrink-proofing agent cannot be precisely specified, so that the same organic shrink-proofing agent cannot be used for the calibration curve. In this case, a calibration curve is created using the organic shrink-proofing agent extracted from the negative electrode of the battery and a separately available organic polymer that shows similar shapes in the ultraviolet-visible absorption spectrum, infrared spectroscopy spectrum, NMR spectrum, etc., and the content of the organic shrink-proofing agent is measured using the ultraviolet-visible absorption spectrum.

[0132] (3-3) Sulfur content in organic shrinkage inhibitors As in (3-1) above, a powder sample of the organic shrink-proofing agent is obtained, and then the sulfur element in 0.1 g of the organic shrink-proofing agent is converted to sulfuric acid by the oxygen combustion flask method. At this time, the powder sample is burned in a flask containing an adsorption solution to obtain an eluate in which sulfate ions are dissolved in the adsorption solution. Next, the sulfur element content (C1) in 0.1 g of the organic shrink-proofing agent is determined by titrating the eluate with barium perchlorate using thorin as an indicator. Next, C1 is multiplied by 10 to calculate the sulfur element content (μmol / g) in the organic shrink-proofing agent per 1 g.

[0133] (3-4) Mw of organic shrinkage inhibitor The Mw of the organic shrinkage inhibitor is measured using the following apparatus under the following conditions. GPC equipment: Build-up GPC system SD-8022 / DP-8020 / AS-8020 / CO-8020 / UV-8020 (Tosoh Corporation) Column: TSKgel G4000SWXL, G2000SWXL (7.8 mm I.D. x 30 cm) (Tosoh Corporation) Detector: UV detector, λ=210nm Eluent: A mixture of 1 mol / L NaCl aqueous solution: acetonitrile (volume ratio = 7:3) Flow rate: 1mL / min. Concentration: 10mg / mL Injection volume: 10μL Standard substance: Sodium polystyrene sulfonate (Mw=275,000, 35,000, 12,500, 7,500, 5,200, 1,680)

[0134] (4) Quantitative analysis of carbonaceous materials and barium sulfate Unpulverized sample A is pulverized, and 50 ml of 20% mass concentration nitric acid is added to 10 g of the pulverized sample, and the mixture is heated for about 20 minutes to dissolve the lead component as lead nitrate. Next, the solution containing lead nitrate is filtered to separate solids such as carbonaceous materials and barium sulfate.

[0135] The obtained solid content is dispersed in water to obtain a dispersion, and then components other than the carbonaceous material and barium sulfate (e.g., reinforcing material) are removed from the dispersion using a sieve. Next, the dispersion is subjected to suction filtration using a membrane filter whose mass has been measured in advance, and the membrane filter is dried together with the filtered sample in a dryer at 110°C. The filtered sample is a mixed sample of the carbonaceous material and barium sulfate. The mass of the membrane filter is subtracted from the total mass of the mixed sample and the membrane filter after drying to obtain the mass of the mixed sample (M m The dried mixed sample is then placed in a crucible together with the membrane filter and incinerated at 700°C or higher. The remaining residue is barium oxide. The mass of barium oxide is converted to the mass of barium sulfate to obtain the mass of barium sulfate (M B ) is calculated. Mass M m From mass M B The mass of the carbonaceous material is calculated by subtracting the above.

[0136] (others) The negative electrode plate can be formed by applying or filling a negative electrode paste onto a negative electrode current collector, aging and drying to prepare an unformed negative electrode plate, and then chemically forming the unformed negative electrode plate. The negative electrode paste is prepared by adding water and sulfuric acid to lead powder, an organic shrinkage inhibitor, and various additives as necessary, and kneading them. When aging, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at a high humidity.

[0137] The formation can be carried out by immersing the plate group including the unformed negative plate in an electrolyte containing sulfuric acid in a lead-acid battery container and charging the plate group. However, the formation may be carried out before assembling the lead-acid battery or the plate group. The formation produces spongy lead.

[0138] (Positive plate) The positive electrode plate of a lead-acid battery can be classified into a paste type, a clad type, and the like. The paste type positive electrode plate includes a positive electrode collector and a positive electrode material. The positive electrode material is held by the positive electrode collector. In the paste type positive electrode plate, the positive electrode material is the positive electrode plate excluding the positive electrode collector. The positive electrode collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include an expanding process and a punching process. It is preferable to use a lattice-shaped collector as the positive electrode collector because it is easy to support the positive electrode material. The clad type positive electrode plate includes a plurality of porous tubes, a core inserted into each tube, a current collecting portion connecting the plurality of cores, a positive electrode material filled in the tube into which the core is inserted, and a link connecting the plurality of tubes. In the clad type positive plate, the positive electrode material does not include the tube, the core metal, the current collector, and the connecting seat. In the clad type positive plate, the core metal and the current collector are collectively referred to as the positive electrode current collector.

[0139] A positive electrode plate may have a mat, pasting paper, or other such material attached to it. Such material (attaching material) is used integrally with the positive electrode plate, and is therefore considered to be included in the positive electrode plate. In addition, when the positive electrode plate includes such material, the positive electrode material is the positive electrode plate excluding the positive electrode current collector and the attaching material in the case of a paste-type positive electrode plate.

[0140] As the lead alloy used for the positive electrode current collector, in terms of corrosion resistance and mechanical strength, Pb-Sb alloy, Pb-Ca alloy, Pb-Ca-Sn alloy are preferable. The positive electrode current collector may have a surface layer. The surface layer and the inner layer of the positive electrode current collector may have different compositions. The surface layer may be formed on a part of the positive electrode current collector. The surface layer may be formed only on the lattice part, only on the edge part, or only on the frame part of the positive electrode current collector.

[0141] The positive electrode material contained in the positive electrode plate contains a positive electrode active material (lead dioxide or lead sulfate) that develops capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives as necessary.

[0142] The unformed paste-type positive plate is obtained by filling a positive current collector with a positive electrode paste, aging and drying. The positive electrode paste is prepared by kneading lead powder, additives, water and sulfuric acid. The unformed clad-type positive plate is formed by filling a porous tube into which a core metal connected by a current collector is inserted with lead powder or lead powder in a slurry form, and connecting a plurality of tubes with a connecting member. Then, the unformed positive plate is formed to obtain a positive plate. The formation can be performed by charging the plate group in a state where the plate group including the unformed positive plate is immersed in an electrolyte containing sulfuric acid in a battery container of a lead-acid battery. However, the formation may be performed before assembling the lead-acid battery or the plate group.

[0143] The formation can be carried out by immersing an electrode plate group including unformed positive plates in an electrolyte solution containing sulfuric acid in a battery container of a lead-acid battery and charging the electrode plate group in this state. However, the formation may also be carried out before assembling the lead-acid battery or the electrode plate group.

[0144] (Separator) A separator can be placed between the negative and positive electrodes. As the separator, a nonwoven fabric and / or a microporous membrane can be used. The thickness and number of separators to be placed between the negative and positive electrodes can be selected according to the distance between the electrodes.

[0145] A nonwoven fabric is a mat in which fibers are intertwined without being woven, and is mainly composed of fibers. For example, 60% by mass or more of the nonwoven fabric is made of fibers. As the fibers, glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers such as polyethylene terephthalate fibers, etc.), pulp fibers, etc. can be used. Among them, glass fibers are preferable. The nonwoven fabric may contain components other than fibers, such as acid-resistant inorganic powders and polymers as binders.

[0146] On the other hand, a microporous membrane is a porous sheet mainly composed of components other than fiber components, and can be obtained, for example, by extruding a composition containing a pore-forming agent (such as a polymer powder and / or oil) into a sheet, and then removing the pore-forming agent to form pores. The microporous membrane is preferably made of an acid-resistant material, and is preferably made mainly of a polymer component. The polymer component is preferably a polyolefin such as polyethylene or polypropylene.

[0147] The separator may be, for example, composed of only a nonwoven fabric or only a microporous membrane. Furthermore, the separator may be, as necessary, a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same materials, or a laminate of different or the same materials with recesses and projections interlocked.

[0148] The separator may be in a sheet shape or may be formed in a bag shape. A sheet-shaped separator may be sandwiched between the positive electrode plate and the negative electrode plate. Also, the electrode plate may be sandwiched between a folded sheet-shaped separator. In this case, the positive electrode plate sandwiched between the folded sheet-shaped separator and the negative electrode plate sandwiched between the folded sheet-shaped separator may be stacked, or one of the positive electrode plate and the negative electrode plate may be sandwiched between the folded sheet-shaped separator and stacked with the other electrode plate. Also, the sheet-shaped separator may be folded into a bellows shape, and the positive electrode plate and the negative electrode plate may be sandwiched between the bellows-shaped separator so that the separator is interposed between them. When a separator folded like an accordion is used, the separator may be arranged so that the folded portion is along the horizontal direction of the lead-acid battery (for example, so that the folded portion is parallel to the horizontal direction) or along the vertical direction (for example, so that the folded portion is parallel to the vertical direction). In a separator folded like an accordion, recesses are formed alternately on both main surfaces of the separator. Since a lug is usually formed on the upper part of the positive electrode plate and the negative electrode plate, when the separator is arranged so that the folded portion is along the horizontal direction of the lead-acid battery, the positive electrode plate and the negative electrode plate are arranged only in the recesses on one main surface side of the separator (that is, a double separator is interposed between the adjacent positive electrode plate and the negative electrode plate). When the separator is arranged so that the folded portion is aligned with the vertical direction of the lead-acid battery, the positive electrode plate can be accommodated in the recess on one main surface side, and the negative electrode plate can be accommodated in the recess on the other main surface side (that is, a single layer of separator can be interposed between adjacent positive and negative electrode plates.) When a pouch-shaped separator is used, the pouch-shaped separator may accommodate either the positive or negative electrode plate.

[0149] In this specification, the up-down direction of the electrode plate means the up-down direction in the vertical direction of the lead-acid battery.

[0150] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid, which may be gelled as necessary. The electrolyte may contain the above-mentioned polymer compound. As in the case of the negative electrode material, the origin of the polymer compound contained in the electrolyte is not particularly limited.

[0151] The concentration of the polymer compound in the electrolyte is, for example, 5000 ppm or less, may be 3000 ppm or less, 2500 ppm or less, 1500 ppm or less, 1000 ppm or less, or 500 ppm or less, based on mass. When the amount of the polymer compound contained in the electrolyte is within such a range, the overcharged electric quantity can be further reduced, and the decrease in charge acceptance can be further suppressed. The concentration of the polymer compound in the electrolyte can be 1 ppm or more, or 5 ppm or more, based on mass.

[0152] The concentration of the polymer compound in the electrolyte may be, by mass, 1 ppm or more (or 5 ppm or more) and 5000 ppm or less, 1 ppm or more (or 5 ppm or more) and 3000 ppm or less, 1 ppm or more (or 5 ppm or more) and 2500 ppm or less, 1 ppm or more (or 5 ppm or more) and 1500 ppm or less, 1 ppm or more (or 5 ppm or more) and 1000 ppm or less, or 1 ppm or more (or 5 ppm or more) and 500 ppm or less.

[0153] The concentration of the polymer compound in the electrolyte is determined for a lead-acid battery in a fully charged state.

[0154] The concentration of the polymer compound in the electrolyte is determined by adding chloroform to a given amount (ml(g)) of electrolyte taken from a fully charged lead-acid battery, mixing it, leaving it to stand and separating it into two layers, and then taking out only the chloroform layer. After repeating this process several times, the chloroform is distilled off under reduced pressure to obtain the chloroform-soluble fraction. An appropriate amount of the chloroform-soluble fraction is dissolved in deuterated chloroform together with 0.0212±0.0001g of TCE, 1 Measure the H-NMR spectrum. The integral value (S a ) and the integral value of the peak due to TCE (S r) and calculate the polymer compound content C in the electrolyte from the following formula: e Request. C e =S a / S r ×N r / N a ×M a / M r ×m r / m1×1000000 (In the formula, M a and N a are the same as above.)

[0155] The electrolyte may optionally contain cations (e.g., metal cations such as sodium ions, lithium ions, magnesium ions, and / or aluminum ions) and / or anions (e.g., anions other than sulfate anions, such as phosphate ions).

[0156] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20°C is, for example, 1.20 or more, and may be 1.25 or more. The specific gravity of the electrolyte at 20°C is 1.35 or less, and preferably 1.32 or less. These lower and upper limits can be combined in any manner. The specific gravity of the electrolyte at 20°C may be 1.20 or more and 1.35 or less, 1.20 or more and 1.32 or less, 1.25 or more and 1.35 or less, or 1.25 or more and 1.32 or less.

[0157] The lead-acid battery can be obtained by a manufacturing method including a step of assembling the lead-acid battery by housing a positive electrode plate, a negative electrode plate, and an electrolyte in a battery case. In the step of assembling the lead-acid battery, the separator is usually disposed between the positive electrode plate and the negative electrode plate. The step of assembling the lead-acid battery may include a step of forming the positive electrode plate and / or the negative electrode plate, as necessary, after the step of housing the positive electrode plate, the negative electrode plate, and the electrolyte in the battery case. The positive electrode plate, the negative electrode plate, the electrolyte, and the separator are each prepared before being housed in the battery case.

[0158] FIG. 1 shows an external appearance of an example of a lead-acid battery according to one embodiment of the present invention. The lead-acid battery 1 includes a battery case 12 that contains a plate group 11 and an electrolyte (not shown). The battery case 12 is divided into a plurality of cell chambers 14 by partition walls 13. Each cell chamber 14 contains one plate group 11. The opening of the battery case 12 is closed by a lid 15 that has a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When refilling with water, the vent plug 18 is removed and refilling liquid is added. The vent plug 18 may have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.

[0159] Each electrode plate group 11 is formed by stacking a plurality of negative electrode plates 2 and positive electrode plates 3 with a separator 4 interposed therebetween. Here, a pouch-shaped separator 4 that accommodates the negative electrode plates 2 is shown, but the shape of the separator is not particularly limited. In a cell chamber 14 located at one end of the battery case 12, a negative electrode shelf portion 6 that connects a plurality of negative electrode plates 2 in parallel is connected to a through connector 8, and a positive electrode shelf portion 5 that connects a plurality of positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 outside the lid 15. In a cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf portion 6, and a through connector 8 is connected to the positive electrode shelf portion 5. The negative electrode column 9 is connected to a negative electrode terminal 16 outside the lid 15. Each through connector 8 passes through a through hole provided in the partition wall 13 to connect the electrode plate groups 11 of adjacent cell chambers 14 in series.

[0160] The positive electrode shelf 5 is formed by welding the lugs provided on the upper part of each positive electrode plate 3 together by a cast-on-strap method or a burning method. The negative electrode shelf 6 is also formed by welding the lugs provided on the upper part of each negative electrode plate 2 together in the same manner as the positive electrode shelf 5.

[0161] A lead-acid battery according to one aspect of the present invention will be described below.

[0162] (1) A battery comprising a positive electrode plate, a negative electrode plate, and an electrolyte; The negative electrode plate comprises a negative electrode material, The negative electrode material contains a polymer compound and a metal element (excluding Pb), The polymer compound is 1 A lead-acid battery having a peak in the range of 3.2 ppm or more and 3.8 ppm or less in the chemical shift of the H-NMR spectrum.

[0163] (2) In the above (1), the polymer compound contains an oxygen atom bonded to an end group and a -CH2- group and / or a -CH< group bonded to the oxygen atom, 1 In the H-NMR spectrum, the ratio of the integral of the peak to the sum of the integral of the peak, the integral of the peak of the hydrogen atom of the -CH- group, and the integral of the peak of the hydrogen atom of the -CH< group may be 50% or more, 80% or more, 85% or more, or 90% or more.

[0164] (3) In the above (1) or (2), the polymer compound is oxyC 2-4 It may contain a repeating structure of alkylene units.

[0165] (4) A battery comprising a positive electrode plate, a negative electrode plate, and an electrolyte; The negative electrode plate comprises a negative electrode material, The negative electrode material is a metal element (excluding Pb) and oxy-C 2-4 and a polymer compound containing a repeating structure of alkylene units.

[0166] (5) In the above (3) or (4), the polymer compound is 2-4 Etherification products of hydroxy compounds having repeating alkylene units and said oxy C 2-4 and at least one selected from the group consisting of esters of hydroxy compounds having a repeating alkylene unit structure, The hydroxy compound is polyC 2-4 Alkylene glycol, oxy C 2-4 Copolymers containing repeating alkylene units and polyols C 2-4 It may be at least one selected from the group consisting of alkylene oxide adducts.

[0167] (6) A battery comprising a positive electrode plate, a negative electrode plate, and an electrolyte; The negative electrode plate comprises a negative electrode material, The negative electrode material includes a first metal element (excluding Pb) and a polymer compound, The polymer compound is oxyC 2-4 Ethers of hydroxy compounds with repeating alkylene units and oxy C 2-4 and at least one selected from the group consisting of esters of hydroxy compounds having a repeating alkylene unit structure, The hydroxy compound is polyC 2-4 Alkylene glycol, oxy C 2-4 Copolymers containing repeating alkylene units and polyols C 2-4 The lead-acid battery comprises at least one selected from the group consisting of alkylene oxide adducts.

[0168] (7) In the above (5) or (6), the etherified product is an etherified --OR compound in which at least a part of the terminal --OH groups of the hydroxy compound are etherified. 2 group (in the formula, R 2 is an organic group, and the organic group R 2 may be a hydrocarbon group.

[0169] (8) In the above (5) or (6), the esterification product is an ester of at least a part of the terminal -OH groups of the hydroxy compound, i.e., -OC(=O)-R 3 group (in the formula, R 3 is an organic group, and the organic group R 3 may be a hydrocarbon group.

[0170] (9) In the above (7) or (8), the hydrocarbon group may be an aliphatic hydrocarbon group.

[0171] (10) In the above (9), the aliphatic hydrocarbon group may be either linear or branched.

[0172] (11) In the above (9) or (10), the number of carbon atoms in the aliphatic hydrocarbon group is, for example, 30 or less, optionally 26 or less or 22 or less, optionally 20 or less or 16 or less, optionally 14 or less or 10 or less, or optionally 8 or less or 6 or less.

[0173] (12) In any one of the above (9) to (11), the aliphatic hydrocarbon group may be an alkyl group or an alkenyl group.

[0174] (13) In the above (12), the alkyl group may have 1 or more carbon atoms, and the alkenyl group may have 2 or more carbon atoms.

[0175] (14) In the above (12) or (13), the alkyl group may be at least one selected from the group consisting of methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, i-pentyl, s-pentyl, 3-pentyl, t-pentyl, n-hexyl, 2-ethylhexyl, n-octyl, n-decyl, i-decyl, lauryl, myristyl, cetyl, stearyl, and behenyl.

[0176] (15) In the above (12) or (13), the alkenyl group is, for example, C 2-30 Alkenyl group or C 2-26 may be an alkenyl group, C 2-22 Alkenyl group or C 2-20 may be an alkenyl group, C 10-20 It may be an alkenyl group.

[0177] (16) In the above (12), (13) or (15), the alkenyl group may be at least one selected from the group consisting of vinyl, 1-propenyl, allyl, palmitoleyl and oleyl.

[0178] (17) In any one of the above (3) to (16), the oxy C 2-4 The repeating structure of the alkylene unit may include at least a repeating structure of an oxypropylene unit.

[0179] (18) In the above (17), the proportion of the oxypropylene unit in the polymer compound (one molecule) may be 5 mol % or more, 10 mol % or more, or 20 mol % or more.

[0180] (19) In any one of the above (1) to (18), the polymer compound may include a compound having an Mn of 500 or more, may include a compound having an Mn of 600 or more, or may include a compound having an Mn of 1000 or more.

[0181] (20) In the above (19), the Mn of the compound may be 20,000 or less, 15,000 or less, 10,000 or less, 5,000 or less, 4,000 or less, or 3,000 or less.

[0182] (21) In any one of the above (1) to (18), the polymer compound may include at least a compound having an Mn of 1,000 or more.

[0183] (22) In the above (21), the Mn of the compound may be 1,000 or more and 20,000 or less, 1,000 or more and 15,000 or less, 1,000 or more and 10,000 or less, 1,000 or more and 5,000 or less, 1,000 or more and 4,000 or less, or 1,000 or more and 3,000 or less.

[0184] (23) In any one of the above (1) to (22), the content of the polymer compound in the negative electrode material may be, on a mass basis, 10 ppm or more, 20 ppm or more, 30 ppm or more, or 40 ppm or more.

[0185] (24) In any one of the above (1) to (23), the content of the polymer compound in the negative electrode material may be, by mass, 500 ppm or less, 400 ppm or less, 320 ppm or less, 300 ppm or less, 200 ppm or less, 150 ppm or less, or 130 ppm or less.

[0186] (25) In any one of the above (1) to (24), the first metal element may include at least one selected from the metal elements of Groups 3 to 14 of the periodic table.

[0187] (26) In any one of the above (1) to (25), the first metal element may include at least one selected from the group consisting of metal elements in Group 10 and Group 11 of the periodic table.

[0188] (27) In any one of the above (1) to (26), the first metal element may include at least one selected from the group consisting of Cu, Ag, and Ni.

[0189] (28) In any one of the above (1) to (27), the content of the first metal element in the negative electrode material may be, on a mass basis, 10 ppm or more, 20 ppm or more, 50 ppm or more, or 100 ppm or more.

[0190] (29) In any one of the above (1) to (28), the content of the first metal element in the negative electrode material may be, on a mass basis, 500 ppm or less, 200 ppm or less, 180 ppm or less, or 150 ppm or less.

[0191] (30) In any one of the above (1) to (29), the mass ratio of the first metal element to the polymer compound contained in the negative electrode material (=first metal element / polymer compound) may be 0.12 or more, 0.15 or more, 0.25 or more, 0.75 or more, or 1.25 or more.

[0192] (31) In any one of the above (1) to (30), the mass ratio of the first metal element to the polymer compound contained in the negative electrode material (=first metal element / polymer compound) may be 2.5 or less, 2.0 or less, or 1.5 or less.

[0193] (32) In any one of the above (1) to (31), the first metal element may include Cu, and the content of Cu in the negative electrode material may be, by mass, 30 ppm or more, 40 ppm or more, 50 ppm or more, or 60 ppm or more.

[0194] (33) In any one of the above (1) to (32), the first metal element may include Cu, and the content of Cu in the negative electrode material may be, by mass, 300 ppm or less, 200 ppm or less, 150 ppm or less, 120 ppm or less, or 100 ppm or less.

[0195] (34) In any one of the above (1) to (33), the first metal element may include Cu, and the mass ratio of Cu to the polymer compound (=Cu / polymer compound) may be 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, or 0.7 or more.

[0196] (35) In any one of the above (1) to (34), the first metal element may include Cu, and the mass ratio of Cu to the polymer compound (=Cu / polymer compound) may be 2.3 or less, 1.6 or less, 1.5 or less, or 1.25 or less.

[0197] (36) In any one of the above (1) to (35), the first metal element may include Ag, and the content of Ag in the negative electrode material may be, by mass, 30 ppm or more, 40 ppm or more, 50 ppm or more, 80 ppm or more, or 90 ppm or more.

[0198] (37) In any one of the above (1) to (36), the first metal element may include Ag, and the content of Ag in the negative electrode material may be, by mass, 350 ppm or less, 300 ppm or less, 200 ppm or less, 190 ppm or less, or 180 ppm or less.

[0199] (38) In any one of the above (1) to (37), the first metal element may include Ag, and the mass ratio of Ag to the polymer compound (=Ag / polymer compound) may be 0.2 or more, 0.25 or more, or 0.5 or more.

[0200] (39) In any one of the above (1) to (38), the first metal element may include Ag, and the mass ratio of Ag to the polymer compound (=Ag / polymer compound) may be 2.5 or less, 2.3 or less, 2 or less, or 1.5 or less.

[0201] (40) In any one of the above (1) to (39), the first metal element may include Ni, and the content of Ni in the negative electrode material may be, on a mass basis, 10 ppm or more, 15 ppm or more, or 20 ppm or more.

[0202] (41) In any one of the above (1) to (40), the first metal element may include Ni, and the content of Ni in the negative electrode material may be, by mass, 150 ppm or less, 100 ppm or less, 70 ppm or less, 60 ppm or less, 50 ppm or less, 40 ppm or less, or 30 ppm or less.

[0203] (42) In any one of the above (1) to (41), the first metal element may contain Ni, and the mass ratio of Ni to the polymer compound (=Ni / polymer compound) may be 0.05 or more, or 0.1 or more.

[0204] (43) In any one of the above (1) to (42), the first metal element may include Ni, and the mass ratio of Ni to the polymer compound (=Ni / polymer compound) may be 1 or less, 0.7 or less, or 0.5 or less.

[0205] (44) Regarding any one of the above (1) to (43), the negative electrode material may contain a metal component containing the first metal element, and the average particle size of the metal component may be 1 μm or less, 500 nm or less, or 300 nm or less.

[0206] (45) Regarding any one of the above (1) to (44), the negative electrode material may contain a metal component that contains the first metal element, and the average particle size of the metal component may be 10 nm or more.

[0207] (46) In any one of the above (1) to (45), the negative electrode material may further contain a carbonaceous material.

[0208] (47) In the above (46), the content of the carbonaceous material in the negative electrode material may be 0.05 mass % or more, or 0.10 mass % or more.

[0209] (48) In the above (46) or (47), the content of the carbonaceous material in the negative electrode material may be 5% by mass or less, or 3% by mass or less.

[0210] (49) In any one of the above (1) to (48), the negative electrode material may further contain an organic shrinkage preventer.

[0211] (50) In the above (49), the organic shrink-preventing agent may be at least one selected from the group consisting of synthetic organic shrink-preventing agents and lignins.

[0212] (51) In the above (49) or (50), the content of the organic shrink-preventing agent in the negative electrode material may be 0.01% by mass or more, or 0.05% by mass or more.

[0213] (52) In any one of the above (49) to (51), the content of the organic shrink-preventing agent in the negative electrode material may be 1.0 mass % or less or 0.5 mass % or less.

[0214] (53) In any one of the above (1) to (52), the electrolytic solution may contain the polymer compound.

[0215] (54) In the above (53), the concentration of the polymer compound in the electrolyte may be, by mass, 5000 ppm or less, 3000 ppm or less, 2500 ppm or less, 1500 ppm or less, 1000 ppm or less, or 500 ppm or less.

[0216] (55) In the above (53) or (54), the concentration of the polymer compound in the electrolyte may be 1 ppm or more, or 5 ppm or more, on a mass basis.

[0217] (56) In any one of the above (1) to (55), the negative electrode material may contain barium sulfate.

[0218] (57) In the above (56), the content of the barium sulfate in the negative electrode material may be 0.05% by mass or more, or 0.10% by mass or more.

[0219] (58) In the above (56) or (57), the content of the barium sulfate in the negative electrode material may be 3% by mass or less or 2% by mass or less.

[0220] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0221] Lead-acid batteries E1 to E15 and R1 to R9 (1) Preparation of lead-acid batteries (a) Preparation of the negative electrode plate The raw materials lead powder, barium sulfate, carbon black, a polymer compound (polypropylene glycol, Mn=2000), and an organic shrinkage inhibitor are mixed with an appropriate amount of sulfuric acid aqueous solution to obtain a negative electrode paste. At this time, the components are mixed so that the content of the polymer compound in the negative electrode material, which is obtained by the procedure described above, is the value shown in Table 1, and the content of the barium sulfate is 0.6 mass%, the content of the carbon black is 0.3 mass%, and the content of the organic shrinkage inhibitor is 0.1 mass%. The negative electrode paste is filled into the mesh part of an expanded lattice made of a Pb-Ca-Sn alloy, and is aged and dried to obtain an unformed negative electrode plate. As the organic shrinkage inhibitor, a condensate of a bisphenol compound with a sulfonic acid group introduced therein and formaldehyde (sulfur element content: 5000 μmol / g, Mw=9600) is used.

[0222] (b) Preparation of the positive electrode plate The raw lead powder is mixed with an aqueous sulfuric acid solution to obtain a positive electrode paste, which is then filled into the mesh of an expanded lattice made of a Pb-Ca-Sn alloy, aged and dried to obtain an unformed positive electrode plate.

[0223] (c) Preparation of test battery The test battery has a rated voltage of 2V and a rated 5-hour rate capacity of 35Ah. The plate assembly of the test battery is composed of seven positive plates and seven negative plates. The negative plates are housed in a pouch-shaped separator made of a microporous polyethylene film and are alternately stacked with the positive plates to form a plate assembly. The plate assembly is housed in a polypropylene container together with an electrolyte, and chemical formation is performed in the container to prepare a liquid-type lead-acid battery. As the electrolyte, an aqueous sulfuric acid solution containing sulfates of the metals shown in Table 1 as the first metal element source is used. The specific gravity of the electrolyte after chemical formation is 1.28 (calculated at 20°C). The first metal element is electrodeposited in the negative electrode material by chemical formation. The concentration of sulfates in the electrolyte and chemical formation conditions (applied current, current flow time, etc.) are adjusted so that the content of the first metal element in the negative electrode material obtained by the above-mentioned procedure becomes the value in Table 1.

[0224] In the lead-acid batteries E1 to E15, the concentration of the polymer compound in the electrolyte determined by the above-mentioned procedure is 500 ppm or less.

[0225] The polymer compound measured by the procedure described above 1 In the H-NMR spectrum, peaks derived from -CH2- of the oxypropylene unit are observed in the chemical shift range of 3.2 ppm to 3.42 ppm, and peaks derived from -CH< and -CH2- of the oxypropylene unit are observed in the chemical shift range of more than 3.42 ppm to 3.8 ppm. 1 In the H-NMR spectrum, the percentage of the integral of the peak between 3.2 ppm and 3.8 ppm to the sum of the integral of this peak, the integral of the peak of the hydrogen atoms of the -CH2- groups bonded to the oxygen atoms, and the integral of the peak of the hydrogen atoms of the -CH< groups bonded to the oxygen atoms, is 98.1%.

[0226] The average particle size of the metal component containing the first metal element contained in the negative electrode material determined by the above-mentioned procedure is within a range of 10 nm to 300 nm.

[0227] (2) Evaluation (a) Charge acceptance The charge at 10 seconds is measured using a fully charged test battery. Specifically, the test battery is discharged at 7A for 30 minutes and left to stand for 1 minute. The test battery is then charged at a constant voltage of 2.4V / cell, and the accumulated charge over this period (charge at 10 seconds) is measured. Both procedures are carried out in a water tank at 25°C ± 2°C. The charge acceptance of each lead-acid battery is evaluated as a percentage of the charge at 10 seconds for lead-acid battery R1, which is set to 100.

[0228] (b) Overcharged electricity The above-mentioned lead acid battery is used under the following conditions. To create a higher overcharge condition than the normal 4-10 minute test specified in JIS D5301, a 1 minute discharge-10 minute charge test (1-10 minute test) is performed at 75°C ±3°C (high temperature light load test). The high temperature light load test is performed by repeating charge and discharge for 1220 cycles. The overcharge quantity of electricity (charge quantity of electricity - discharge quantity of electricity) in each cycle up to the 1220th cycle is totaled and averaged to determine the overcharge quantity of electricity (Ah) per cycle. The overcharge quantity of electricity is evaluated as a ratio (%) when the overcharge quantity of electricity (Ah) per cycle of lead-acid battery R1 is set to 100.

[0229] The results for the lead-acid batteries E1 to E15 and R1 to R9 are shown in Table 1. In the table, "-" indicates that the content of the first metal element was below the detection limit.

[0230] [Table 1] As shown in Table 1, when the negative electrode material contains a polymer compound, the charge acceptance is lower than when the negative electrode material does not contain a polymer compound (for example, compare R1 with R5 (7% decrease)). In addition, the first metal element alone does not have the effect of suppressing the decrease in charge acceptance (compare R1 with R2 to R4). However, when the negative electrode material contains a polymer compound, the decrease in charge acceptance is suppressed by including the first metal element in the negative electrode material (E1 to E15). In this way, a synergistic effect is obtained in the effect of suppressing the decrease in charge acceptance by combining the polymer compound and the first metal element. Therefore, it is presumed that the polymer compound and the first metal element interact with each other.

[0231] In addition, in E1 to E15, even though the negative electrode material contains the first metal element, the overcharge quantity of electricity is significantly reduced (comparison of E1 to E15 with R2 to R4). This is believed to be due to the increase in hydrogen overvoltage caused by the presence of the polymer compound. Although the above-mentioned lead-acid battery is an example in which a synthetic organic shrinkage preventer is used, the same or similar effects as those described above can be obtained when lignins are used.

[0232] 《Lead acid battery E16~E18》 The polymer compounds shown in Table 2 are used. The components of the negative electrode paste are mixed so that the content of the polymer compound in the negative electrode material determined by the above-mentioned procedure is the value shown in Table 2. Except for this, test batteries are prepared and evaluated in the same manner as the lead-acid battery E9. Regarding the polymer compounds, 1 In the H-NMR spectrum, the percentage of the integral of the peak between 3.2 ppm and 3.8 ppm to the total integral of this peak, the integral of the peak of the hydrogen atoms of the -CH2- groups bonded to the oxygen atoms, and the integral of the peak of the hydrogen atoms of the -CH< groups bonded to the oxygen atoms, is 97.6% to 99.7%.

[0233] 《Lead acid battery E19~E21》 The polymer compounds shown in Table 2 are used. The components of the negative electrode paste are mixed so that the content of the polymer compound in the negative electrode material determined by the above-mentioned procedure is the value shown in Table 2. Except for this, test batteries are produced and evaluated in the same manner as the lead-acid battery E11. Regarding the polymer compounds, 1 In the H-NMR spectrum, the percentage of the integral of the peak between 3.2 ppm and 3.8 ppm to the total integral of this peak, the integral of the peak of the hydrogen atoms of the -CH2- groups bonded to the oxygen atoms, and the integral of the peak of the hydrogen atoms of the -CH< groups bonded to the oxygen atoms, is 97.6% to 99.7%.

[0234] The results for the lead-acid batteries E16 to E21 are shown in Table 2. The results for the lead-acid batteries R1, E9, and E11 are also shown in Table 2. In the table, "-" indicates that the content of the first metal element was below the detection limit.

[0235] [Table 2]

[0236] As shown in Table 2, oxyC 2-4Even when an ether or ester of a hydroxy compound having a repeating alkylene unit structure is used, the amount of overcharge electricity is reduced and the decrease in charge acceptance is suppressed. [Industrial Applicability]

[0237] The lead-acid battery according to one aspect of the present invention can be suitably used, for example, as a power source for starting vehicles (automobiles, motorcycles, etc.) and as a power source for industrial power storage devices for electric vehicles (forklifts, etc.). Note that these uses are merely examples and are not limited to these uses. [Explanation of symbols]

[0238] 1:Lead acid battery 2: Negative plate 3: Positive plate 4: Separator 5: Positive electrode shelf 6: Negative electrode shelf 7: Positive pole 8: Through connector 9: Negative pole 11: Plate group 12:Battery container 13: Bulkhead 14: Cell Room 15: Lid 16: Negative terminal 17: Positive terminal 18: Liquid outlet plug

Claims

1. The battery includes a positive electrode plate, a negative electrode plate, and an electrolyte solution. The negative electrode plate comprises a negative electrode material, The negative electrode material contains a polymer compound and a metal element (excluding Pb), The metal element includes at least one selected from the group consisting of metal elements of Group 10 and Group 11 of the Periodic Table, The polymer compound is 1 A lead-acid battery having a peak in the range of 3.2 ppm to 3.8 ppm in the chemical shift of the H-NMR spectrum.

2. A lead-acid battery as described in claim 1, wherein the content of the polymer compound in the negative electrode material is 10 ppm or more and 400 ppm or less by mass.

3. A battery comprising a positive electrode plate, a negative electrode plate, and an electrolyte, The negative electrode plate comprises a negative electrode material, The negative electrode material contains a polymer compound and a metal element (excluding Pb), The polymer compound has a peak in the range of 3.2 ppm to 3.8 ppm in chemical shift of 1 H-NMR spectrum, A lead-acid battery, wherein the content of the polymer compound in the negative electrode material is 10 ppm or more and 400 ppm or less by mass.

4. The lead acid battery according to claim 3, wherein the metal element includes at least one selected from metal elements of Groups 3 to 14 of the periodic table.

5. The polymer compound has an oxygen atom bonded to a terminal group and a —CH 2 - and / or -CH< groups, The above 1 In the H-NMR spectrum, the integral value of the peak and the integral value of the -CH 2 The lead acid battery according to any one of claims 1 to 4, wherein the ratio of the integral value of the peak of the hydrogen atom of the - group to the integral value of the peak of the hydrogen atom of the -CH< group in the total is 85% or more.

6. The polymer compound is oxyC 2-4 The lead acid battery according to any one of claims 1 to 5, comprising a repeating structure of alkylene units.

7. The battery includes a positive electrode plate, a negative electrode plate, and an electrolyte solution. The negative electrode plate comprises a negative electrode material, The negative electrode material is a metal element (excluding Pb) and oxy-C 2-4 a polymer compound containing a repeating structure of an alkylene unit, The metal element includes at least one selected from the group consisting of Group 10 metal elements and Group 11 metal elements of the periodic table.

8. A lead-acid battery as described in claim 7, wherein the content of the polymer compound in the negative electrode material is 10 ppm or more and 400 ppm or less by mass.

9. A battery comprising a positive electrode plate, a negative electrode plate, and an electrolyte, The negative electrode plate comprises a negative electrode material, The negative electrode material contains a metal element (excluding Pb) and a polymer compound containing a repeating structure of an oxyC 2-4 alkylene unit, A lead-acid battery, wherein the content of the polymer compound in the negative electrode material is 10 ppm or more and 400 ppm or less by mass.

10. The lead-acid battery according to claim 9, wherein the metal element includes at least one selected from the metal elements of groups 3 to 14 of the periodic table.

11. The polymer compound is 2-4 Etherification products of hydroxy compounds having repeating alkylene units and the above-mentioned oxy C 2-4 and at least one selected from the group consisting of esters of hydroxy compounds having a repeating alkylene unit structure, The hydroxy compound is polyC 2-4 Alkylene glycol, oxy C 2-4 A copolymer containing an alkylene repeating unit and a polyol C 2-4 The lead acid battery according to any one of claims 6 to 10, which is at least one selected from the group consisting of alkylene oxide adducts.

12. The oxy C 2-4 The lead acid battery according to any one of claims 6 to 11, wherein the repeating structure of the alkylene unit includes at least a repeating structure of an oxypropylene unit.

13. The lead-acid battery according to claim 12 , wherein the polymer compound includes at least a compound having a number average molecular weight of 1000 or more.

14. The lead acid battery according to any one of claims 1 to 13, wherein the metal element includes at least one selected from the group consisting of Cu, Ag, and Ni.

15. The lead acid battery according to any one of claims 1 to 14, wherein the content of the metal element in the negative electrode material is 10 ppm or more and 500 ppm or less by mass.

Citation Information

Patent Citations

  • Graphene composite carbon for lead-acid battery and preparation method of graphene composite carbon

    CN106099056A

  • Negative lead paste for lead carbon battery and negative plate

    CN108630937A

  • Lead-acid battery

    JP1985182662A

  • Lead-acid battery

    JP1997147869A

  • Lead-acid battery and its activation method

    JP2000149980A